Effects of surgical implantation of electronic tags in fishes: a review and meta-analysis - Mitchell B. Shorgan; Graham D. Raby; Amber L. Fedus; Bradley E. Howell; Laura S. E. Haniford; Leah C. Howitt; Natalie V. Klinard; Jordan K. Matley; Jacob W. Brownscombe; Steven J. Cooke; Aaron T. Fisk (Reviews in Fish Biology and Fisheries, 2026)

A history of chronic adolescent stress attenuates cued fear-potentiated startle in adult female Wistar rats - Amy J. Wegener; Molly M. Hyer; Zuby Okafor; Grace Young; Chloe Burns; Emilie Bjerring; Samya Dyer; Paul Howell; Susie Turkson; Tanja Jovanovic; Gretchen N. Neigh (Psychopharmacology, 2026)
Rationale Post-traumatic stress disorder (PTSD) is a stress and trauma-related disorder that is largely characterized by hyperarousal to fear-based cues. N-methyl-D-aspartate (NMDA) receptors are key mediators of fear learning behaviors. Altered NMDA receptor signaling is a hallmark of PTSD pathology that impacts fear memory learning and extinction processes. Objectives In the current study, we tested whether exposing adolescent rats to a mixed modality stress paradigm of repeated restraint, social defeat, and individual housing (chronic adolescent stress; CAS) decreased immunoreactivity of the NMDA subunit NR2B in the central amygdala in adulthood. We sought to determine the impact of a peripherally administered NMDA receptor agonist D-cycloserine (DCS) intervention to enhance extinction of learned fear in CAS animals. Methods Upon reaching adulthood, CAS animals were exposed to a cued fear-potentiated startle paradigm. DCS was administered immediately following the first of two extinction sessions with the goal of enhancing extinction learning. Results CAS females expressed impaired fear extinction compared to non-stressed females, but were not influenced by the DCS intervention. Males overall were able to successfully learn fear extinction regardless of stress history, however, DCS treatment may have increased fear potentiated startle responsivity in males with a history of stress. Conclusions These data suggest that chronic stress during adolescence modifies NMDA receptor expression, but functional impacts on cued fear learning differ by sex and require additional approaches to better understand the mechanisms underlying stress-induced impairments in fear learning behaviors.

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Effects of environmental conditions on mate fidelity in a socially monogamous seabird - Sue Lewis; Adam Butler; Sarah Wanless; Mark A. Newell; Michael P. Harris; Sarah J. Burthe; Carrie M. Gunn; Richard J. Howells; Francis Daunt (Animal Behaviour, 2025)

Re-assessment of a large archosaur dentary from the Late Triassic of South Wales, United Kingdom - Owain Evans; Cindy Howells; Nathan Wintle; Michael J. Benton (Proceedings of the Geologists' Association, 2025)

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Navigating danger: Watercraft-related mortality of sea turtles in the United States Atlantic and Gulf coastal waters - Mariana M.P.B. Fuentes; Brian A. Stacy; Susan G. Barco; Robert A. DiGiovanni; Karen M. Dourdeville; Kimberly F. Durham; Mark Faherty; Sarah A. Finn; Allen M. Foley; Matthew H. Godfrey; Robert F. Hardy; Lyndsey N. Howell; et al. (Biological Conservation, 2025)

Application of a population status model on several recreational lake trout (Salvelinus namaycush) fisheries in Manitoba, Canada - Giulio Navarroli; Bradley E. Howell; Andrew W. R. Klein; Eric J. Mullen; Olivier Morissette; Michael D. Rennie; Caleb T. Hasler (Environmental Biology of Fishes, 2025)

Harnessing primary, secondary and tertiary genepools for durable wheat disease resistance - Anisa Blower; Rumiana V. Ray; Stephen Rawsthorne; Phil J. Howell; Fiona J. Leigh; Kostya Kanyuka (Theoretical and Applied Genetics, 2025)
Bread wheat ( Triticum aestivum ), a cornerstone of global food security contributing ~ 20% of daily caloric intake, faces increasing vulnerability to rapidly evolving pathogens. This is due in part to a narrowed genetic base following domestication and modern breeding. Wild and ancestral wheat relatives are critical reservoirs of disease resistance genes for breeding new, resilient varieties. This review explores the contributions of primary, secondary, and tertiary genepools of wheat to disease resistance, highlighting loci effective against fungal pathogens that threaten European wheat production. It examines the challenges of alien gene transfer including crossability barriers, hybrid necrosis, and suppressor loci and reviews modern breeding tools such as marker-assisted selection, genomic selection, and genome editing for harnessing exotic germplasm. By synthesising current knowledge, this review highlights the vital contribution of ancestral wheat germplasm in enhancing the resilience and productivity of future wheat crops against increasing biotic stresses.

Growth patterns of three Hydrilla verticillata biotypes in the United States - Jens P. Beets; Kara J. Foley; Benjamin P. Sperry; Andrew W. Howell; Robert J. Richardson (Aquatic Botany, 2025)

You and your cat: Factors affecting quality of human-cat relationship - David J. Menor-Campos; Inmaculada Peña-Vela; Tiffani Howell (Journal of Veterinary Behavior, 2025)

Regional differentiation in somatic growth and maturation attributes for loggerhead sea turtles (Caretta caretta) in the Northwest Atlantic - Larisa Avens; Margaret M. Lamont; Allen M. Foley; Benjamin M. Higgins; Lyndsey N. Howell; Gretchen Lovewell; Donna J. Shaver; Brian A. Stacy; J. Shelby Walker; Jamie M. Clark; Amy A. Wallace; Hannah B. Vander Zanden (Marine Biology, 2025)

Rapamycin Treatment Reduces Brain Pericyte Constriction in Ischemic Stroke - Daniel J. Beard; Lachlan S. Brown; Gary P. Morris; Yvonne Couch; Bryan A. Adriaanse; Christina Simoglou Karali; Anna M. Schneider; David W. Howells; Zoran B. Redzic; Brad A. Sutherland; Alastair M. Buchan (Translational Stroke Research, 2025)
The contraction and subsequent death of brain pericytes may play a role in microvascular no-reflow following the reopening of an occluded artery during ischemic stroke. Mammalian target of rapamycin (mTOR) inhibition has been shown to reduce motility/contractility of various cancer cell lines and reduce neuronal cell death in stroke. However, the effects of mTOR inhibition on brain pericyte contraction and death during ischemia have not yet been investigated. Cultured pericytes exposed to simulated ischemia for 12 h in vitro contracted after less than 1 h, which was about 7 h prior to cell death. Rapamycin significantly reduced the rate of pericyte contraction during ischemia; however, it did not have a significant effect on pericyte viability at any time point. Rapamycin appeared to reduce pericyte contraction through a mechanism that is independent of changes in intracellular calcium. Using a mouse model of middle cerebral artery occlusion, we showed that rapamycin significantly increased the diameter of capillaries underneath pericytes and increased the number of open capillaries 30 min following recanalisation. Our findings suggest that rapamycin may be a useful adjuvant therapeutic to reduce pericyte contraction and improve cerebral reperfusion post-stroke.

Corrigendum to “Multiple-species resistance to avermectin/milbemycin anthelmintics on beef cattle farms in Georgia, USA” [Vet. Parasitol. 336 (2025) 110435] - Leonor Sicalo Gianechini; Kelsey L. Paras; Melissa M. George; Sue B. Howell; Bob Storey; Matthew J. Denwood; Ray M. Kaplan (Veterinary Parasitology, 2025)

Characterization of adult hippocampal neurogenesis in adult and aged genetically diverse mice - Adele E. Finch; Avery D. McNamara; Kristen D. Onos; Kelly J. Keezer; Gareth R. Howell; Ashley E. Webb (GeroScience, 2025)
Adult hippocampal neurogenesis—the generation of new neurons in the adult brain—declines with age, contributing to cognitive deficits in aging. While the majority of mammalian studies on neurogenesis have utilized inbred mouse strains, these models do not fully capture the genetic diversity of humans, limiting the translational relevance of their findings. The Diversity Outbred (DO) mouse model, a genetically heterogeneous population, provides a promising alternative to traditional inbred strains. In this study, we investigated how genetic diversity influences hippocampal neurogenesis by comparing neurogenesis in adult and aged Diversity Outbred (DO) mice with the commonly used C57BL/6J inbred strain. While both strains exhibited a decline in neurogenesis with age, DO mice showed significantly lower levels of neurogenesis compared to C57BL/6J mice, even in young adults. Additionally, we observed that the wild-derived CAST/EiJ strain, one of the eight founder strains in the DO model, contributed to this reduction in neurogenesis. Our findings highlight the importance of genetic diversity in neurogenesis research and suggest that the DO model may better represent human genetic diversity associated with age-related decline in neurogenesis.

Field measurements of steelhead trout Oncorhynchus mykiss distribution, swimming behavior and response to water current exposure in a sea cage - M. Chambers; M. Doherty; M. Coogan; C. Rillahan; J. DeCew; P. Lader; W.H. Howell (Aquaculture, 2025)

Multiple-species resistance to avermectin anthelmintics on beef cattle farms in Georgia, USA - Leonor Sicalo Gianchini; Kelsey L. Paras; Melissa M. George; Sue B. Howell; Bob Storey; Matthew J. Denwood; Ray M. Kaplan (Veterinary Parasitology, 2025)

Estimated golden eagle mortality from wind turbines in the western United States - Jay V. Gedir; Matthew J. Gould; Brian A. Millsap; Paige E. Howell; Guthrie S. Zimmerman; Emily R. Bjerre; Hillary M. White (Biological Conservation, 2025)

Development and application of a genetic baseline to inform bull trout (Salvelinus confluentus) passage and conservation in the Snake River - John S. Hargrove; Thomas A. Delomas; Matthew R. Campbell; Philip J. Howell; Audrey C. Harris; Richard Wilkison (Conservation Genetics, 2025)

Co‐Existence Slows Diversification in Experimental Populations of E. coli and P. fluorescens - Gareth Howells; Aysha L. Sezmis; Christopher Blake; Michael J. McDonald (Environmental Microbiology, 2025)
Microbes grown in heterogeneous laboratory environments can rapidly diversify into multiple, coexisting variants. While the genetic and evolutionary mechanisms of laboratory adaptive radiations are well studied, how the presence of other species alters the outcomes of diversification is less well understood. To test the effect of co‐culture growth on the Pseudomonas fluorescens SBW25 adaptive radiation, Escherichia coli and P. fluorescens were cultured in monoculture and co‐culture for 8 weeks. In P. fluorescens monoculture, Wrinkly and Smooth Spreader types rapidly evolved and were maintained over 8 weeks, while E. coli monocultures evolved two colony types, a big and a small colony variant. In contrast, we found that in co‐culture, E. coli did not evolve small colony variants. Whole genome sequencing revealed the genetic basis of possible co‐culture specific adaptations in both E. coli and P. fluorescens . Altogether, our data support that the presence of multiple species changed the outcome of adaptive radiation.

An analysis and successful benchmarking of the Chapman-Enskog-like (CEL) continuum kinetic closure approach algorithm in NIMROD - Joseph R. Jepson; Chris C. Hegna; Eric D. Held; Carl R. Sovinec; J. Andrew Spencer; Eric C. Howell (Computer Physics Communications, 2025)

An eight-founder wheat MAGIC population allows fine-mapping of flowering time loci and provides novel insights into the genetic control of flowering time - Laure Fourquet; Tobias Barber; Camila Campos-Mantello; Phil Howell; Beata Orman-Ligeza; Lawrence Percival-Alwyn; Gemma A. Rose; Hester Sheehan; Tally I. C. Wright; Friedrich Longin; Tobias Würschum; Dario Novoselovic; et al. (Theoretical and Applied Genetics, 2024)
Flowering time synchronizes reproductive development with favorable environmental conditions to optimize yield. Improved understanding of the genetic control of flowering will help optimize varietal adaptation to future agricultural systems under climate change. Here, we investigate the genetic basis of flowering time in winter wheat ( Triticum aestivum L.) using an eight-founder multi-parent advanced generation intercross (MAGIC) population. Flowering time data was collected from field trials across six growing seasons in the United Kingdom, followed by genetic analysis using a combination of linear modelling, simple interval mapping and composite interval mapping, using either single markers or founder haplotype probabilities. We detected 57 quantitative trait loci (QTL) across three growth stages linked to flowering time, of which 17 QTL were identified only when the major photoperiod response locus Ppd-D1 was included as a covariate. Of the 57 loci, ten were identified using all genetic mapping approaches and classified as ‘major’ QTL, including homoeologous loci on chromosomes 1B and 1D, and 4A and 4B. Additional Earliness per se flowering time QTL were identified, along with growth stage- and year-specific effects. Furthermore, six of the main-effect QTL were found to interact epistatically with Ppd-D1 . Finally, we exploited residual heterozygosity in the MAGIC recombinant inbred lines to Mendelize the Earliness per se QTL QFt.niab-5A.03 , which was confirmed to modulate flowering time by at least four days. This work provides detailed understanding of the genetic control of phenological variation within varieties relevant to the north-western European wheat genepool, aiding informed manipulation of flowering time in wheat breeding.

Quantifying Virtual Field Trip Efficiency - J. H. Pugsley; J. A. Howell; A. J. Hartley; S. J. Buckley; M. Chmielewska; N. Naumann; N. J. Schofield; R. Brackenridge (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2024)
The efficiency of virtual field trips (VFTs) compared to their physical counterparts, is often regarded as one of their key benefits. Virtual field trips are typically more time, cost and environmentally efficient and logistically easier to plan and execute. This is largely due to the lack of travel, however, the nature of these efficiencies, which is essential for deciding whether a trip should be virtual, physical or blended, have not previously been quantified. Here we present a quantitative evaluation of several measures of efficiency, using data from a like-for-like comparison between 10 day long virtual and physical field trips to Utah, USA, from the University of Aberdeen, UK. For this case study, our results demonstrate that virtual field trips are more efficient across all the categories of time, cost, environmental impact, and logistics. In addition to saved air travel days at the start and end of the physical trip, a further 33.3% of the time on the physical field trip was spent travelling (walking and driving). This time saving allowed an additional 16 localities to be visited on the virtual field trip. The virtual field trip localities also ran in an order that best suited the geological narrative rather than their geographic location which the physical field trip was restricted by. Flights and driven kilometres for the physical trip produced c. 4 t of carbon dioxide equivalent (CO 2 ) per student. The virtual trip produce <1% of the CO 2 and was comparable to a typical teaching week, making it significantly more environmentally efficient. The cost of the virtual trip was negligible compared to that of the physical trip (saving up to £ 3000 GBP per student). These findings were compared to the fulfilment of learning outcomes, quantified primarily through questionnaires, the student responses suggest that the PFT and VFT perceptions of learning outcomes were generally comparable. Efficiency is not the only measure of a successful field trip, with other parameters such as social cohesion and embodiment within the outdoor environment that must also be considered when planning a field trip. Therefore, the authors do not advocate or support an abandonment of physical field trips. Rather, this study aims to provide a first attempt to quantify efficiency to inform decision making when planning field training.

An Integrative Approach to Weight Management – Patient-centered Medical Home, Wellness Center, and Pharmacology - M. Coy; S. Troxell; B. Roper; K. Russo; O. Erinne; A. Luker; S. Shalak; J. Howell; J. Duhart (Journal of the Academy of Nutrition and Dietetics, 2024)

Synthesizing the spatial functionality of contemporary stock assessment software to identify future needs for next generation assessment platforms - Aaron M. Berger; Caren Barceló; Daniel R. Goethel; Simon D. Hoyle; Patrick D. Lynch; Jeremy McKenzie; Alistair Dunn; André E. Punt; Richard D. Methot; John Hampton; Clay E. Porch; Richard McGarvey; et al. (Fisheries Research, 2024)

A new winter wheat genetic resource harbors untapped diversity from synthetic hexaploid wheat - Tally I. C. Wright; Richard Horsnell; Bethany Love; Amanda J. Burridge; Keith A. Gardner; Robert Jackson; Fiona J. Leigh; Aleksander Ligeza; Sigrid Heuer; Alison R. Bentley; Philip Howell (Theoretical and Applied Genetics, 2024)
Key message The NIAB_WW_SHW_NAM population, a large nested association mapping panel, is a useful resource for mapping QTL from synthetic hexaploid wheat that can improve modern elite wheat cultivars. Abstract The allelic richness harbored in progenitors of hexaploid bread wheat ( Triticum aestivum L.) is a useful resource for addressing the genetic diversity bottleneck in modern cultivars. Synthetic hexaploid wheat (SHW) is created through resynthesis of the hybridisation events between the tetraploid ( Triticum turgidum subsp. durum Desf.) and diploid ( Aegilops tauschii Coss.) bread wheat progenitors. We developed a large and diverse winter wheat nested association mapping (NAM) population (termed the NIAB_WW_SHW_NAM) consisting of 3241 genotypes derived from 54 nested back-cross 1 (BC 1 ) populations, each formed via back-crossing a different primary SHW into the UK winter wheat cultivar ‘Robigus’. The primary SHW lines were created using 15 T. durum donors and 47 Ae. tauschii accessions that spanned the lineages and geographical range of the species. Primary SHW parents were typically earlier flowering, taller and showed better resistance to yellow rust infection ( Yr ) than ‘Robigus’. The NIAB_WW_SHW_NAM population was genotyped using a single nucleotide polymorphism (SNP) array and 27 quantitative trait loci (QTLs) were detected for flowering time, plant height and Yr resistance. Across multiple field trials, a QTL for Yr resistance was found on chromosome 4D that corresponded to the Yr28 resistance gene previously reported in other SHW lines. These results demonstrate the value of the NIAB_WW_SHW_NAM population for genetic mapping and provide the first evidence of Yr28 working in current UK environments and genetic backgrounds. These examples, coupled with the evidence of commercial wheat breeders selecting promising genotypes, highlight the potential value of the NIAB_WW_SHW_NAM to variety improvement.

Trajectories and tipping points of piñon–juniper woodlands after fire and thinning - Michala L. Phillips; Cara Lauria; Tova Spector; John B. Bradford; Catherine Gehring; Brooke B. Osborne; Armin Howell; Edmund E. Grote; Renee J. Rondeau; Gillian M. Trimber; Benjamin Robinson; Sasha C. Reed (Global Change Biology, 2024)
Piñon–juniper (PJ) woodlands are a dominant community type across the Intermountain West, comprising over a million acres and experiencing critical effects from increasing wildfire. Large PJ mortality and regeneration failure after catastrophic wildfire have elevated concerns about the long‐term viability of PJ woodlands. Thinning is increasingly used to safeguard forests from fire and in an attempt to increase climate resilience. We have only a limited understanding of how fire and thinning will affect the structure and function of PJ ecosystems. Here, we examined vegetation structure, microclimate conditions, and PJ regeneration dynamics following ~20 years post‐fire and thinning treatments. We found that burned areas had undergone a state shift that did not show signs of returning to their previous state. This shift was characterized by (1) distinct plant community composition dominated by grasses; (2) a lack of PJ recruitment; (3) a decrease in the sizes of interspaces in between plants; (4) lower abundance of late successional biological soil crusts; (5) lower mean and minimum daily soil moisture values; (6) lower minimum daily vapor pressure deficit; and (7) higher photosynthetically active radiation. Thinning created distinct plant communities and served as an intermediate between intact and burned communities. More intensive thinning decreased PJ recruitment and late successional biocrust cover. Our results indicate that fire has the potential to create drier and more stressful microsite conditions, and that, in the absence of active management following fire, there may be shifts to persistent ecological states dominated by grasses. Additionally, more intensive thinning had a larger impact on community structure and recruitment than less intensive thinning, suggesting that careful consideration of goals could help avoid unintended consequences. While our results indicate the vulnerability of PJ ecosystems to fire, they also highlight management actions that could be adapted to create conditions that promote PJ re‐establishment.

A risk assessment for the remote ocean: the case of the South East Atlantic - Holly J. Niner; Siân E. Rees; Giulia La Bianca; Kirsty A. McQuaid; Kerry L. Howell (Frontiers in Marine Science, 2024)
Degradation of the natural world and associated ecosystem services is attributed to a historical failure to include its ‘value’ in decision-making. Uncertainty in the quantification of the relationship between natural capital ‘assets’ that give rise to critical societal benefits and people is one reason for the omission of these values from natural resource management. As this uncertainty increases in marine systems and further still with distance from the coast, the connection between society and natural capital assets is less likely to be included adequately in decision-making. Natural capital assets of Areas Beyond National Jurisdiction (ABNJ), including those of the deep sea, are distant but are known to generate many benefits for society, from the diffuse and broad-scale benefits of climate regulation to the provision of wild fish for food. While our understanding of the precise relationships (the status of asset stocks, ecosystem functions and processes) that control the availability of ecosystem services and the flows of benefits is limited, this does not preclude opening a discourse on how these natural capital assets could best be managed to continue to benefit society. Here we apply a natural capital approach to the South East Atlantic ABNJ, one of the least scientifically understood regions of the planet, and develop a framework for risk assessment. We do this by describing the benefit flows from the natural capital assets of the region, appraising how activities are creating pressures on these flows and whether the controls for these pressures protect them. Our risk register highlights how governance currently favours the protection of direct (extractive) benefit flows from natural capital assets of the region, which are primarily targeted for financial benefit. Without a systems-based framework that can account for the cumulative pressures on natural capital assets their status, associated ecosystem services and benefits are at risk. Such an approach is essential to capture and protect the foundational and often diffuse connections between marine natural capital and global society.

Ciguatera poisoning in French Polynesia: A review of the distribution and toxicity of Gambierdiscus spp., and related impacts on food web components and human health - M. Chinain; C. Gatti Howell; M. Roué; A. Ung; K. Henry; T. Revel; P. Cruchet; J. Viallon; H.T. Darius (Harmful Algae, 2023)

DESIGNER fraction concept unmasks minor bioactive constituents in red clover (Trifolium pratense L.) - Ryan Hitzman; Gonzalo R. Malca-Garcia; Caitlin Howell; Hyun-Young Park; J. Brent Friesen; Huali Dong; Tareisha Dunlap; James B. McAlpine; Guenter Vollmer; Maarten C. Bosland; Dejan Nikolić; David C. Lankin; et al. (Phytochemistry, 2023)

Correction to: The Effects of Long-term, Low-dose β-N-methylamino-L-alanine (BMAA) Exposures in Adult SODG93R Transgenic Zebrafish - Ryan D. Weeks; Sandra A. Banack; Shaunacee Howell; Preethi Thunga; James S. Metcalf; Adrian J. Green; Paul A. Cox; Antonio Planchart (Neurotoxicity Research, 2023)

The Effects of Long-term, Low-dose β-N-methylamino-l-alanine (BMAA) Exposures in Adult SODG93R Transgenic Zebrafish - Ryan D. Weeks; Sandra A. Banack; Shaunacee Howell; Preethi Thunga; James S. Metcalf; Adrian J. Green; Paul A. Cox; Antonio Planchart (Neurotoxicity Research, 2023)

Overview of the search for signs of space weathering on the low-albedo asteroid (101955) Bennu - B.E. Clark; A. Sen; X.-D. Zou; D.N. DellaGiustina; S. Sugita; N. Sakatani; M. Thompson; D. Trang; E. Tatsumi; M.A. Barucci; M. Barker; H. Campins; et al. (Icarus, 2023)

Moonquake-triggered mass wasting processes on icy satellites - Mackenzie M. Mills; Robert T. Pappalardo; Mark P. Panning; Erin J. Leonard; Samuel M. Howell (Icarus, 2023)

Broad-scale benthic habitat classification of the South Atlantic - Kirsty A. McQuaid; Amelia E.H. Bridges; Kerry L. Howell; Tiago B.R. Gandra; Vitor de Souza; Jock C. Currie; Oliver T. Hogg; Tabitha R.R. Pearman; James B. Bell; Lara J. Atkinson; Diane Baum; Jarbas Bonetti; et al. (Progress in Oceanography, 2023)

A standardised ecosystem services framework for the deep sea - Giulia La Bianca; Sian Rees; Martin J. Attrill; Amanda T. Lombard; Kirsty A. McQuaid; Holly J. Niner; Henk van Rein; Kerry J. Sink; Kerry L. Howell (Frontiers in Marine Science, 2023)
Despite its remoteness, human activity has impacted the deep sea and changes to the structure and function of deep-sea ecosystems are already noticeable. In terrestrial and shallow water marine environments, demonstrating how ecosystems support human well-being has been instrumental in setting policy and management objectives for sustainable resource use. Foundational to this approach is a framework of ecosystem service (ES) classification and a synthesis of the knowledge base, which can then be used to structure decision-support tools such as ecosystem accounts or Environmental Impact Assessments. At present, no such framework exists for the deep sea. There is thus an urgent need to determine and assess the ES provided by deep-sea habitats and species before (potentially irreversible) decisions are made about deep-sea habitat use and governance. As a first step towards the incorporation of ES in such decision-making, we undertake two systematic reviews of the scientific literature based on the principles of the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) systematic process. This was to define a comparative ES framework and synthesise the current evidence base for how deep-sea habitats support ecosystem services. Our framework proposes four supporting services, three regulating services, four provisioning services and three cultural services for which there is an established and growing body of evidence for the role of deep-sea habitats. The ES framework presented here provides a structure for deep-sea ecosystem services. In its next phase of development, this could provide the foundation for the development of habitat-ecosystem service matrices, which are a critical component for truly accounting for ES in decision-making, particularly spatial management. This framework has significant implications for deep-sea management, conservation and policy, as it provides an ecosystem services-based tool that can be used in any deep-sea ecosystems management across the planet, and it also shows how critical these data gaps are for today’s decisions and how seriously they should be considered in decision-making processes.

Six years of demography data for 11 reef coral species - Joshua S. Madin; Andrew H. Baird; Sean R. Connolly; Maria A. Dornelas; Mariana Álvarez‐Noriega; Michael J. McWilliam; Miguel Barbosa; Shane A. Blowes; Paulina Cetina‐Heredia; Alec P. Christie; Vivian R. Cumbo; Marcela Diaz; et al. (Ecology, 2023)
Scleractinian corals are colonial animals with a range of life‐history strategies, making up diverse species assemblages that define coral reefs. We tagged and tracked ~30 colonies from each of 11 species during seven trips spanning 6 years (2009–2015) to measure their vital rates and competitive interactions on the reef crest at Trimodal Reef, Lizard Island, Australia. Pairs of species were chosen from five growth forms in which one species of the pair was locally rare (R) and the other common (C). The sampled growth forms were massive ( Goniastrea pectinata [R] and G. retiformis [C]), digitate ( Acropora humilis [R] and A. cf. digitifera [C]), corymbose ( A. millepora [R] and A. nasuta [C]), tabular ( A. cytherea [R] and A. hyacinthus [C]) and arborescent ( A. robusta [R] and A. intermedia [C]). An extra corymbose species with intermediate abundance, A. spathulata was included when it became apparent that A. millepora was too rare on the reef crest, making the 11 species in total. The tagged colonies were visited each year in the weeks prior to spawning. During visits, two or more observers each took two or three photographs of each tagged colony from directly above and on the horizontal plane with a scale plate to track planar area. Dead or missing colonies were recorded and new colonies tagged to maintain ~30 colonies per species throughout the 6 years of the study. In addition to tracking tagged corals, 30 fragments were collected from neighboring untagged colonies of each species for counting numbers of eggs per polyp (fecundity); and fragments of untagged colonies were brought into the laboratory where spawned eggs were collected for biomass and energy measurements. We also conducted surveys at the study site to generate size structure data for each species in several of the years. Each tagged colony photograph was digitized by at least two people. Therefore, we could examine sources of error in planar area for both photographers and outliners. Competitive interactions were recorded for a subset of species by measuring the margins of tagged colony outlines interacting with neighboring corals. The study was abruptly ended by Tropical Cyclone Nathan (Category 4) that killed all but nine of the more than 300 tagged colonies in early 2015. Nonetheless, these data will be of use to other researchers interested in coral demography and coexistence, functional ecology, and parametrizing population, community, and ecosystem models. The data set is not copyright restricted, and users should cite this paper when using the data.

Integrated ecosystem assessment around islands of the tropical South Mid-Atlantic Ridge - Amanda R. Rodrigues; Sergio R. Floeter; Vicente Gomes; Débora S. Ferrari; Vinicius J. Giglio; Fernanda C. Silva; Ana M. R. Liedke; Carlos E. L. Ferreira; Kerry Howell; Maria A. Gasalla (Frontiers in Marine Science, 2023)
The South Mid Atlantic Ridge comprises three main oceanic islands in the equatorial and tropical portions of the Atlantic Ocean. These islands are isolated from each other and equidistant from both the continental margins of South America and Africa, sharing common patterns but with different types of human use and pressures. Moreover, the areas beyond national jurisdiction between those islands are visited and exploited by distant fishing fleets and include large areas of shipping activity for commodities. Here, a pioneering integrated ecosystem assessment (IEA) process is constructed for the region among Saint Peter and Saint Paul’s Archipelago (Brazil), Saint Helena Island and Ascension Island (UK overseas territories). For that, we used a qualitative assessment of risks arising from anthropogenic activities, representing a novel contribution to the field. The Options for Delivering Ecosystem-Based Marine Management (ODEMM) approach was applied to trace sector–pressure–component pathways. A ‘linkage framework’ was outlined including pressures affecting each ecosystem component, and supported a process of knowledge attributions that scored the impact risks. All results were validated with regional stakeholders through workshops, including local and international management bodies, non-governmental organizations (NGOs) and scientists. The approach focused on a significant area among encompassing the open ocean, shallow and deep-sea biomes, analyzing the main sectors and pressures affecting the ecological components. Our results identified 14 sectors and 16 key pressures associated with 23 ecosystem components, totaling 780 impact chains. Fishing, shipping, wastewater, and tourism/recreation appeared as the top impacting sectors. Fishing and shipping were the most connected with ecosystem components links. Litter, species extraction, contaminants, and bycatch were the pressures that had the highest risk of impact values. Lastly, demersal and pelagic fish and pelagic and demersal elasmobranchs were the groups with the highest risk related to overall impacts, which were supported by local and regional evidence from long term monitoring programs and local studies. Our study demonstrated that these seemingly pristine islands and oceanic waters are already experiencing human impacts that should be addressed by local both conservation measures and international agreements. We also highlight the pressures that should be prioritized for better monitoring and policy, as well as those linkage components that have been less investigated.

Diversity and transparency in gynecologic oncology clinical trials - Mary Katherine Montes de Oca; Elizabeth P. Howell; Daniel Spinosa; Hope Knochenhauer; Benjamin J. Peipert; Eric Severson; Shakti Ramkissoon; Tomi F. Akinyemiju; Rebecca A. Previs (Cancer Causes & Control, 2023)

Transplant experiments demonstrate that larger brains are favoured in high‐competition environments in Trinidadian killifish - Kaitlyn J. Howell; Matthew R. Walsh (Ecology Letters, 2023)
The extent to which the evolution of a larger brain is adaptive remains controversial. Trinidadian killifish ( Anablepsoides hartii ) are found in sites that differ in predation intensity; fish that experience decreased predation and increased intraspecific competition exhibit larger brains. We evaluated the connection between brain size and fitness (survival and growth) when killifish are found in their native habitats and when fish are transplanted from sites with predators to high‐competition sites that lack predators. Selection for a larger brain was absent within locally adapted populations. Conversely, there was a strong positive relationship between brain size and growth in transplanted but not resident fish in high‐competition environments. We also observed significantly larger brain sizes in the transplanted fish that were recaptured at the end of the experiment versus those that were not. Our results provide experimental support that larger brains increase fitness and are favoured in high‐competition environments.

Extended gene panel testing in lobular breast cancer - Elke M. van Veen; D. Gareth Evans; Elaine F. Harkness; Helen J. Byers; Jamie M. Ellingford; Emma R. Woodward; Naomi L. Bowers; Andrew J. Wallace; Sacha J. Howell; Anthony Howell; Fiona Lalloo; William G. Newman; et al. (Familial Cancer, 2022)
Purpose : Lobular breast cancer (LBC) accounts for ~ 15% of breast cancer. Here, we studied the frequency of pathogenic germline variants (PGVs) in an extended panel of genes in women affected with LBC. Methods : 302 women with LBC and 1567 without breast cancer were tested for BRCA1/2 PGVs. A subset of 134 LBC affected women who tested negative for BRCA1/2 PGVs underwent extended screening, including: ATM, CDH1, CHEK2, NBN, PALB2, PTEN, RAD50, RAD51D, and TP53. Results : 35 PGVs were identified in the group with LBC, of which 22 were in BRCA1/2 . Ten actionable PGVs were identified in additional genes ( ATM (4), CDH1 (1), CHEK2 (1), PALB2 (2) and TP53 (2)). Overall, PGVs in three genes conferred a significant increased risk for LBC. Odds ratios (ORs) were: BRCA1 : OR = 13.17 (95%CI 2.83–66.38; P = 0.0017), BRCA2 : OR = 10.33 (95%CI 4.58–23.95; P < 0.0001); and ATM: OR = 8.01 (95%CI 2.52–29.92; P = 0.0053). We did not detect an increased risk of LBC for PALB2, CDH1 or CHEK2 . Conclusion : The overall PGV detection rate was 11.59%, with similar rates of BRCA1/2 (7.28%) PGVs as for other actionable PGVs (7.46%), indicating a benefit for extended panel genetic testing in LBC. We also report a previously unrecognised association of pathogenic variants in ATM with LBC.

White matter variability, cognition, and disorders: a systematic review - Stephanie J. Forkel; Patrick Friedrich; Michel Thiebaut de Schotten; Henrietta Howells (Brain Structure and Function, 2022)
Inter-individual differences can inform treatment procedures and—if accounted for—have the potential to significantly improve patient outcomes. However, when studying brain anatomy, these inter-individual variations are commonly unaccounted for, despite reports of differences in gross anatomical features, cross-sectional, and connectional anatomy. Brain connections are essential to facilitate functional organization and, when severed, cause impairments or complete loss of function. Hence, the study of cerebral white matter may be an ideal compromise to capture inter-individual variability in structure and function. We reviewed the wealth of studies that associate cognitive functions and clinical symptoms with individual tracts using diffusion tractography. Our systematic review indicates that tractography has proven to be a sensitive method in neurology, psychiatry, and healthy populations to identify variability and its functional correlates. However, the literature may be biased, as the most commonly studied tracts are not necessarily those with the highest sensitivity to cognitive functions and pathologies. Additionally, the hemisphere of the studied tract is often unreported, thus neglecting functional laterality and asymmetries. Finally, we demonstrate that tracts, as we define them, are not correlated with one, but multiple cognitive domains or pathologies. While our systematic review identified some methodological caveats, it also suggests that tract–function correlations might still be a promising tool in identifying biomarkers for precision medicine. They can characterize variations in brain anatomy, differences in functional organization, and predicts resilience and recovery in patients.

A dry future for the Everglades favors invasive herpetofauna - Hunter J. Howell; Giacomo L. Delgado; Alyssa C. Wood; Leila M. Thompson; Eric A. Cline; Christopher A. Searcy (Biological Invasions, 2021)

d ‐canavanine affects peptidoglycan structure, morphogenesis and fitness in Rhizobiales - Alena Aliashkevich; Matthew Howell; Pamela J. B. Brown; Felipe Cava (Environmental Microbiology, 2021)
Summary The bacterial cell wall is made of peptidoglycan (PG), a polymer that is essential for maintenance of cell shape and survival. Many bacteria alter their PG chemistry as a strategy to adapt their cell wall to external challenges. Therefore, identifying these environmental cues is important to better understand the interplay between microbes and their habitat. Here, we used the soil bacterium Pseudomonas putida to uncover cell wall modulators from plant extracts and found canavanine (CAN), a non‐proteinogenic amino acid. We demonstrated that cell wall chemical editing by CAN is licensed by P. putida BSAR, a broad‐spectrum racemase which catalyses production of dl ‐CAN from l ‐CAN, which is produced by many legumes. Importantly, d ‐CAN diffuses to the extracellular milieu thereby having a potential impact on other organisms inhabiting the same niche. Our results show that d ‐CAN alters dramatically the PG structure of Rhizobiales (e.g., Agrobacterium tumefaciens , Sinorhizobium meliloti ), impairing PG crosslinkage and cell division. Using A. tumefaciens , we demonstrated that the detrimental effect of d ‐CAN is suppressed by a single amino acid substitution in the cell division PG transpeptidase penicillin binding protein 3a. Collectively, this work highlights the role of amino acid racemization in cell wall chemical editing and fitness.

Widespread bleaching in the One Tree Island lagoon (Southern Great Barrier Reef) during record-breaking temperatures in 2020 - Megan K. B. Nolan; Sebastian Schmidt-Roach; Andrew R. Davis; Manuel Aranda; Emily J. Howells (Environmental Monitoring and Assessment, 2021)

Physiological diversity among sympatric, conspecific endosymbionts of coral (Cladocopium C1acro) from the Great Barrier Reef - V. H. Beltrán; E. Puill-Stephan; E. Howells; A. Flores-Moya; M. Doblin; E. Núñez-Lara; V. Escamilla; T. López; M. J. H. van Oppen (Coral Reefs, 2021)

Evaluation of Dosing Strategies of N-acetylcysteine for Acetaminophen Toxicity in Patients Greater than 100 Kilograms: Should the Dosage Cap Be Used? - Regan A. Baum; Jordan A. Woolum; Abby M. Bailey; Molly M. Howell; Kyle A. Weant; LeeAnn Geraghty; Sanjay Mohan; Ashley N. Webb; Mark K. Su; Peter Akpunonu; Adam J. Dugan; Leanne Atchison; et al. (Journal of Medical Toxicology, 2021)

Foraging Habits of Green Sea Turtles (Chelonia mydas) in the Northwestern Gulf of Mexico - Lyndsey N. Howell; Donna J. Shaver (Frontiers in Marine Science, 2021)
Knowledge of green turtle ( Chelonia mydas ) foraging ecology in the northwestern Gulf of Mexico (GOM) is critical as populations begin to recover from heavy harvesting in prior centuries. We present a comprehensive long-term assessment of green turtle diets from carcasses salvaged from 1987 to 2014 along the Texas coast. Digestive tract contents were examined from 420 green turtles, ranging in size from 7.3 to 86.0 cm in straight carapace length (SCL max ). Green turtles as small as 16.2 cm SCL max recruit from the oceanic environment to nearshore foraging habitat in the northwestern GOM and consume macroalgae principally. A successive shift in diet and habitat to inshore seagrasses was evident by the seagrass-dominated diet of turtles larger than 30 cm SCL max . Animal matter remained a frequently ingested diet item suggesting these immature green turtles are better classified as omnivores. The overall evidence indicates that Texas’ recovering green turtle assemblage is exhibiting foraging plasticity within seagrass meadows changing species composition and density.

Refining Fisheries Advice With Stock-Specific Ecosystem Information - Jacob W. Bentley; Mathieu G. Lundy; Daniel Howell; Steven E. Beggs; Alida Bundy; Francisco de Castro; Clive J. Fox; Johanna J. Heymans; Christopher P. Lynam; Debbi Pedreschi; Pia Schuchert; Natalia Serpetti; et al. (Frontiers in Marine Science, 2021)
Although frequently suggested as a goal for ecosystem-based fisheries management, incorporating ecosystem information into fisheries stock assessments has proven challenging. The uncertainty of input data, coupled with the structural uncertainty of complex multi-species models, currently makes the use of absolute values from such models contentious for short-term single-species fisheries management advice. Here, we propose a different approach where the standard assessment methodologies can be enhanced using ecosystem model derived information. Using a case study of the Irish Sea, we illustrate how stock-specific ecosystem indicators can be used to set an ecosystem-based fishing mortality reference point (F ECO ) within the “Pretty Good Yield” ranges for fishing mortality which form the present precautionary approach adopted in Europe by the International Council for the Exploration of the Sea (ICES). We propose that this new target, F ECO , can be used to scale fishing mortality down when the ecosystem conditions for the stock are poor and up when conditions are good. This approach provides a streamlined quantitative way of incorporating ecosystem information into catch advice and provides an opportunity to operationalize ecosystem models and empirical indicators, while retaining the integrity of current assessment models and the F MSY -based advice process.

Using Habitat Classification to Assess Representativity of a Protected Area Network in a Large, Data-Poor Area Targeted for Deep-Sea Mining - Kirsty A. McQuaid; Martin J. Attrill; Malcolm R. Clark; Amber Cobley; Adrian G. Glover; Craig R. Smith; Kerry L. Howell (Frontiers in Marine Science, 2020)
Extractive activities in the ocean are expanding into the vast, poorly studied deep sea, with the consequence that environmental management decisions must be made for data-poor seafloor regions. Habitat classification can support marine spatial planning and inform decision-making processes in such areas. We present a regional, top–down, broad-scale, seafloor-habitat classification for the Clarion-Clipperton Fracture Zone (CCZ), an area targeted for future polymetallic nodule mining in abyssal waters in the equatorial Pacific Ocean. Our classification uses non-hierarchical, k-medoids clustering to combine environmental correlates of faunal distributions in the region. The classification uses topographic variables, particulate organic carbon flux to the seafloor, and is the first to use nodule abundance as a habitat variable. Twenty-four habitat classes are identified, with large expanses of abyssal plain and smaller classes with varying topography, food supply, and substrata. We then assess habitat representativity of the current network of protected areas (called Areas of Particular Environmental Interest) in the CCZ. Several habitat classes with high nodule abundance are common in mining exploration claims, but currently receive little to no protection in APEIs. There are several large unmanaged areas containing high nodule abundance on the periphery of the CCZ, as well as smaller unmanaged areas within the central CCZ, that could be considered for protection from mining to improve habitat representativity and safeguard regional biodiversity.

Knowledge of the Relationship Between Breastfeeding and Breast Cancer Risk Among Racial and Ethnic Minority Women - Jamilia R. Sly; Sarah J. Miller; Linda Thelemaque; Fahd Yazdanie; Rhoda Sperling; Fahimeh Sasan; Elizabeth A. Howell; Holly Loudon; Lina Jandorf (Journal of Cancer Education, 2020)

A Blueprint for an Inclusive, Global Deep-Sea Ocean Decade Field Program - Kerry L. Howell; Ana Hilário; A. Louise Allcock; David M. Bailey; Maria Baker; Malcolm R. Clark; Ana Colaço; Jon Copley; Erik E. Cordes; Roberto Danovaro; Awantha Dissanayake; Elva Escobar; et al. (Frontiers in Marine Science, 2020)
The ocean plays a crucial role in the functioning of the Earth System and in the provision of vital goods and services. The United Nations (UN) declared 2021–2030 as the UN Decade of Ocean Science for Sustainable Development. The Roadmap for the Ocean Decade aims to achieve six critical societal outcomes (SOs) by 2030, through the pursuit of four objectives (Os). It specifically recognizes the scarcity of biological data for deep-sea biomes, and challenges the global scientific community to conduct research to advance understanding of deep-sea ecosystems to inform sustainable management. In this paper, we map four key scientific questions identified by the academic community to the Ocean Decade SOs: (i) What is the diversity of life in the deep ocean? (ii) How are populations and habitats connected? (iii) What is the role of living organisms in ecosystem function and service provision? and (iv) How do species, communities, and ecosystems respond to disturbance? We then consider the design of a global-scale program to address these questions by reviewing key drivers of ecological pattern and process. We recommend using the following criteria to stratify a global survey design: biogeographic region, depth, horizontal distance, substrate type, high and low climate hazard, fished/unfished, near/far from sources of pollution, licensed/protected from industry activities. We consider both spatial and temporal surveys, and emphasize new biological data collection that prioritizes southern and polar latitudes, deeper (> 2000 m) depths, and midwater environments. We provide guidance on observational, experimental, and monitoring needs for different benthic and pelagic ecosystems. We then review recent efforts to standardize biological data and specimen collection and archiving, making “sampling design to knowledge application” recommendations in the context of a new global program. We also review and comment on needs, and recommend actions, to develop capacity in deep-sea research; and the role of inclusivity - from accessing indigenous and local knowledge to the sharing of technologies - as part of such a global program. We discuss the concept of a new global deep-sea biological research program ‘ Challenger 150 ,’ highlighting what it could deliver for the Ocean Decade and UN Sustainable Development Goal 14.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Annual outbreaks of coral disease coincide with extreme seasonal warming - E. J. Howells; G. O. Vaughan; T. M. Work; J. A. Burt; D. Abrego (Coral Reefs, 2020)

Localized outbreaks of coral disease on Arabian reefs are linked to extreme temperatures and environmental stressors - Greta Smith Aeby; Emily Howells; Thierry Work; David Abrego; Gareth J. Williams; Lisa M. Wedding; Jamie M. Caldwell; Monica Moritsch; John A. Burt (Coral Reefs, 2020)
The Arabian Peninsula borders the hottest reefs in the world, and corals living in these extreme environments can provide insight into the effects of warming on coral health and disease. Here, we examined coral reef health at 17 sites across three regions along the northeastern Arabian Peninsula (Persian Gulf, Strait of Hormuz and Oman Sea) representing a gradient of environmental conditions. The Persian Gulf has extreme seasonal fluctuations in temperature and chronic hypersalinity, whereas the other two regions experience more moderate conditions. Field surveys identified 13 coral diseases including tissue loss diseases of unknown etiology (white syndromes) in Porites, Platygyra , Dipsastraea , Cyphastrea, Acropora and Goniopora ; growth anomalies in Porites, Platygyra and Dipsastraea ; black band disease in Platygyra , Dipsastraea , Acropora, Echinopora and Pavona ; bleached patches in Porites and Goniopora and a disease unique to this region, yellow-banded tissue loss in Porites . The most widespread diseases were Platygyra growth anomalies (52.9% of all surveys), Acropora white syndrome (47.1%) and Porites bleached patches (35.3%). We found a number of diseases not yet reported in this region and found differential disease susceptibility among coral taxa. Disease prevalence was higher on reefs within the Persian Gulf (avg. 2.05%) as compared to reefs within the Strait of Hormuz (0.46%) or Oman Sea (0.25%). A high number of localized disease outbreaks (8 of 17 sites) were found, especially within the Persian Gulf (5 of 8 sites). Across all regions, the majority of variation in disease prevalence (82.2%) was associated with the extreme temperature range experienced by these corals combined with measures of organic pollution and proximity to shore. Thermal stress is known to drive a number of coral diseases, and thus, this region provides a platform to study disease at the edge of corals’ thermal range.

Use of standardized methods to improve extinction‐risk classification - Caitlin C. Mothes; Stephanie L. Clements; Dishane K. Hewavithana; Hunter J. Howell; Aaron S. David; Nicole D. Leventhal; Christopher A. Searcy (Conservation Biology, 2020)
Standardized classification methods based on quantifiable risk metrics are critical for evaluating extinction threats because they increase objectivity, consistency, and transparency of listing decisions. Yet, in the United States, neither federal nor state agencies use standardized methods for listing species for legal protection, which could put listing decisions at odds with the magnitude of the risk. We used a recently developed set of quantitative risk metrics for California herpetofauna as a case study to highlight discrepancies in listing decisions made without standardized methods. We also combined such quantitative metrics with classification tree analysis to attempt to increase the transparency of previous listing decisions by identifying the criteria that had inherently been given the most weight. Federally listed herpetofauna in California scored significantly higher on the risk‐metric spectrum than those not federally listed, whereas state‐listed species did not score any higher than species that were not state listed. Based on classification trees, state endemism was the most important predictor of listing status at the state level and distribution trend (decline in a species’ range size) and population trend (decline in a species’ abundance at localized sites) were the most important predictors at the federal level. Our results emphasize the need for governing bodies to adopt standardized methods for assessing conservation risk that are based on quantitative criteria. Such methods allow decision makers to identify criteria inherently given the most weight in determining listing status, thus increasing the transparency of previous listing decisions, and produce an unbiased comparison of conservation threat across all species to promote consistency, efficiency, and effectiveness of the listing process.

Corals in the hottest reefs in the world exhibit symbiont fidelity not flexibility - Emily J. Howells; Andrew G. Bauman; Grace O. Vaughan; Benjamin C. C. Hume; Christian R. Voolstra; John A. Burt (Molecular Ecology, 2020)
Reef‐building corals are at risk of extinction from ocean warming. While some corals can enhance their thermal limits by associating with dinoflagellate photosymbionts of superior stress tolerance, the extent to which symbiont communities will reorganize under increased warming pressure remains unclear. Here we show that corals in the hottest reefs in the world in the Persian Gulf maintain associations with the same symbionts across 1.5 years despite extreme seasonal warming and acute heat stress (≥35°C). Persian Gulf corals predominantly associated with Cladocopium (clade C) and most also hosted Symbiodinium (clade A) and/or Durusdinium (clade D). This is in contrast to the neighbouring and milder Oman Sea, where corals associated with Durusdinium and only a minority hosted background levels of Cladocopium . During acute heat stress, the higher prevalence of Symbiodinium and Durusdinium in bleached versus nonbleached Persian Gulf corals indicates that genotypes of these background genera did not confer bleaching resistance. Within symbiont genera, the majority of ITS2 rDNA type profiles were unique to their respective coral species, confirming the existence of host‐specific symbiont lineages. Notably, further differentiation among Persian Gulf sites demonstrates that symbiont populations are either isolated or specialized over tens to hundreds of kilometres. Thermal tolerance across coral species was associated with the prevalence of a single ITS2 intragenomic sequence variant (C3gulf), definitive of the Cladocopium thermophilum group. The abundance of C3gulf was highest in bleaching‐resistant corals and at warmer sites, potentially indicating a specific symbiont genotype (or set of genotypes) that may play a role in thermal tolerance that warrants further investigation. Together, our findings indicate that co‐evolution of host–Symbiodiniaceae partnerships favours fidelity rather than flexibility in extreme environments and under future warming.

Comparison of the Hepatotoxic Potential of Two Treatments for Autosomal-Dominant Polycystic Kidney DiseaseUsing Quantitative Systems Toxicology Modeling - J. L. Woodhead; L. Pellegrini; L. K. M. Shoda; B. A. Howell (Pharmaceutical Research, 2020)
Purpose Autosomal-dominant polycystic kidney disease (ADPKD) is an orphan disease with few current treatment options. The vasopressin V 2 receptor antagonist tolvaptan is approved in multiple countries for the treatment of ADPKD, however its use is associated with clinically significant drug-induced liver injury. Methods In prior studies, the potential for hepatotoxicity of tolvaptan was correctly predicted using DILIsym®, a quantitative systems toxicology (QST) mathematical model of drug-induced liver injury. In the current study, we evaluated lixivaptan, another proposed ADPKD treatment and vasopressin V 2 receptor antagonist, using DILIsym®. Simulations were conducted that assessed the potential for lixivaptan and its three main metabolites to cause hepatotoxicity due to three injury mechanisms: bile acid accumulation, mitochondrial dysfunction, and oxidative stress generation. Results of these simulations were compared to previously published DILIsym results for tolvaptan. Results No ALT elevations were predicted to occur at the proposed clinical dose for lixivaptan, in contrast to previously published simulation results for tolvaptan. As such, lixivaptan was predicted to have a markedly lower risk of hepatotoxicity compared to tolvaptan with respect to the hepatotoxicity mechanisms represented in DILIsym. Conclusions These results demonstrate the potential for using QST methods to differentiate drugs in the same class for their potential to cause hepatotoxicity.

DNA content equivalence in haploid and diploid maize leaves - D. Santeramo; J. Howell; Y. Ji; W. Yu; W. Liu; T. Kelliher (Planta, 2020)
Main conclusion The qPCR assay developed to differentiate haploid and diploid maize leaf samples was unsuccessful due to DNA content difference. Haploid cells are packed more closely together with less cellular expansion. Abstract Increased ploidy content (> 2 N) directly correlates with increased cell size in plants, but few studies have examined cell morphology in plants with reduced ploidy (i.e., haploids). To pioneer a scalable new ploidy test, we compared DNA content and cellular morphology of haploid and diploid maize leaves. The amount of genomic DNA recovered from standardized leaf-punch samples was equivalent between these two ploidy types, while both epidermal and mesophyll cell types were smaller in haploid plants. Pavement cells had a substantially smaller size than mesophyll cells, and this effect was more pronounced in the abaxial epidermis. Interveinal distance and guard cell size were significantly reduced in haploids, but the cell percentage comprising stomata did not change. These results confirm the direct correlation between ploidy content and cell size in plants, and suggest that reduced cell expansion predominantly explains DNA content equivalence between haploid and diploid samples, confounding efforts to develop a haploid detection method using DNA content.

Correction to: Effects of New Zealand blackcurrant extract on sport climbing performance - J. A. Potter; C. I. Hodgson; M. Broadhurst; L. Howell; J. Gilbert; M. E. T. Willems; I. C. Perkins (European Journal of Applied Physiology, 2020)

Effects of New Zealand blackcurrant extract on sport climbing performance - J. A. Potter; C. I. Hodgson; M. Broadhurst; L. Howell; J. Gilbert; M. E. T. Willems; I. C. Perkins (European Journal of Applied Physiology, 2020)

Naturalised status of exotic conifers in New Zealand - Clayson J. Howell (New Zealand Journal of Botany, 2019)
This paper provides an assessment of the naturalisation status all exotic conifers present in New Zealand using existing herbarium specimens as qualifiers. A total; of 371 exotic taxa are confirmed as having been introduced for cultivation which represents 63% of world conifers that are non‐native to New Zealand. In strong contrast to indigenous conifers, introduced conifers are predominantly from the Pineaceae and Cupressaceae families. Naturalised conifers are a major issue for southern hemisphere countries, this paper confirms a total of 57 exotic conifer taxa as wild in New Zealand, including 15 new taxa described as wild since the last comprehensive update. Conifers from the Rocky Mountain and Eastern Asiatic Botanical Regions are prominent among introduced taxa, but naturalised taxa frequently originate from Madrean and Circumboreal Regions. Many of the taxa previously reported as wild have expanded their New Zealand range considerably since their distributions were last described. Despite these increases, most exotic conifers in New Zealand likely occupy a relatively small proportion of the area in which they could establish. The ongoing naturalisation and spread of exotic conifers illustrate the significant environmental weed threat posed by this group.

Should unaffected female BRCA2 pathogenic variant carriers be told there is little or no advantage from risk reducing mastectomy? - D. Gareth Evans; Sacha J. Howell; Anthony Howell (Familial Cancer, 2019)

Combining Distribution and Dispersal Models to Identify a Particularly Vulnerable Marine Ecosystem - Rebecca E. Ross; Edward J. G. Wort; Kerry L. Howell (Frontiers in Marine Science, 2019)

Balanced harvest: concept, policies, evidence, and management implications - Shijie Zhou; Jeppe Kolding; Serge M. Garcia; Michael J. Plank; Alida Bundy; Anthony Charles; Cecilie Hansen; Mikko Heino; Daniel Howell; Nis S. Jacobsen; David G. Reid; Jake C. Rice; et al. (Reviews in Fish Biology and Fisheries, 2019)

Deconstructing compassionate conservation - Matt W. Hayward; Alex Callen; Benjamin L. Allen; Guy Ballard; Femke Broekhuis; Cassandra Bugir; Rohan H. Clarke; John Clulow; Simon Clulow; Jennifer C. Daltry; Harriet T. Davies‐Mostert; Peter J. S. Fleming; et al. (Conservation Biology, 2019)
Compassionate conservation focuses on 4 tenets: first, do no harm; individuals matter; inclusivity of individual animals; and peaceful coexistence between humans and animals. Recently, compassionate conservation has been promoted as an alternative to conventional conservation philosophy. We believe examples presented by compassionate conservationists are deliberately or arbitrarily chosen to focus on mammals; inherently not compassionate; and offer ineffective conservation solutions. Compassionate conservation arbitrarily focuses on charismatic species, notably large predators and megaherbivores. The philosophy is not compassionate when it leaves invasive predators in the environment to cause harm to vastly more individuals of native species or uses the fear of harm by apex predators to terrorize mesopredators. Hindering the control of exotic species (megafauna, predators) in situ will not improve the conservation condition of the majority of biodiversity. The positions taken by so‐called compassionate conservationists on particular species and on conservation actions could be extended to hinder other forms of conservation, including translocations, conservation fencing, and fertility control. Animal welfare is incredibly important to conservation, but ironically compassionate conservation does not offer the best welfare outcomes to animals and is often ineffective in achieving conservation goals. Consequently, compassionate conservation may threaten public and governmental support for conservation because of the limited understanding of conservation problems by the general public.

The effects of training population design on genomic prediction accuracy in wheat - Stefan McKinnon Edwards; Jaap B. Buntjer; Robert Jackson; Alison R. Bentley; Jacob Lage; Ed Byrne; Chris Burt; Peter Jack; Simon Berry; Edward Flatman; Bruno Poupard; Stephen Smith; et al. (Theoretical and Applied Genetics, 2019)

Correction to: Pronounced long-term trends in year-round diet composition of the European shag Phalacrocorax aristotelis - Richard J. Howells; Sarah J. Burthe; Jonathan A. Green; Michael P. Harris; Mark A. Newell; Adam Butler; Sarah Wanless; Francis Daunt (Marine Biology, 2019)

Pronounced long-term trends in year-round diet composition of the European shag Phalacrocorax aristotelis - Richard J. Howells; Sarah J. Burthe; Jonathan A. Green; Michael P. Harris; Mark A. Newell; Adam Butler; Sarah Wanless; Francis Daunt (Marine Biology, 2018)

Genomic and transcriptomic signals of thermal tolerance in heat‐tolerant corals ( Platygyra daedalea ) of the Arabian/Persian Gulf - Nathan L. Kirk; Emily J. Howells; David Abrego; John A. Burt; Eli Meyer (Molecular Ecology, 2018)
Scleractinian corals occur in tropical regions near their upper thermal limits and are severely threatened by rising ocean temperatures. However, several recent studies have shown coral populations can harbour genetic variation in thermal tolerance. Here, we have extended these approaches to study heat tolerance of corals in the Persian/Arabian Gulf, where heat‐tolerant local populations experience extreme summer temperatures (up to 36°C). To evaluate whether selection has depleted genetic variation in thermal tolerance, estimate potential future adaptive responses and understand the functional basis for these corals’ unusual heat tolerance, we conducted controlled crosses in the Gulf coral Platygyra daedalea . Heat tolerance is highly heritable in this population ( h 2 = 0.487–0.748), suggesting substantial potential for adaptive responses to selection for elevated temperatures. To identify genetic markers associated with this variation, we conducted genomewide SNP genotyping in parental corals and tested for relationships between paternal genotype and offspring thermal tolerance. Resulting multilocus SNP genotypes explained a large fraction of variation in thermal tolerance in these crosses (69%). To investigate the functional basis of these differences in thermal tolerance, we profiled transcriptional responses in tolerant and susceptible families, revealing substantial sire effects on transcriptional responses to thermal stress. We also studied sequence variation in these expressed sequences, identifying alleles and functional groups of differentially expressed genes associated with thermal tolerance. Our findings demonstrate that corals in this population harbour extensive genetic variation in thermal tolerance, and heat‐tolerant phenotypes differ in both gene sequences and transcriptional stress responses from their susceptible counterparts.

Species-specific nitrogenase activity in lichen-dominated biological soil crusts from the Colorado Plateau, USA - Terry J. Torres-Cruz; Armin J. Howell; Robin H. Reibold; Theresa A. McHugh; Mackenzie A. Eickhoff; Sasha C. Reed (Plant and Soil, 2018)

The Role of Steroid Hormones in Breast and Effects on Cancer Stem Cells - Denis G. Alferez; Bruno M. Simões; Sacha J. Howell; Robert B. Clarke (Current Stem Cell Reports, 2018)

Species-Specific Coral Calcification Responses to the Extreme Environment of the Southern Persian Gulf - Emily J. Howells; Glenn Dunshea; Dain McParland; Grace O. Vaughan; Scott F. Heron; Morgan S. Pratchett; John A. Burt; Andrew G. Bauman (Frontiers in Marine Science, 2018)

Energy conserving thermoregulatory patterns and lower disease severity in a bat resistant to the impacts of white-nose syndrome - Marianne S. Moore; Kenneth A. Field; Melissa J. Behr; Gregory G. Turner; Morgan E. Furze; Daniel W. F. Stern; Paul R. Allegra; Sarah A. Bouboulis; Chelsey D. Musante; Megan E. Vodzak; Matthew E. Biron; Melissa B. Meierhofer; et al. (Journal of Comparative Physiology B, 2018)

Projecting Marine Mammal Distribution in a Changing Climate - Gregory K. Silber; Matthew D. Lettrich; Peter O. Thomas; Jason D. Baker; Mark Baumgartner; Elizabeth A. Becker; Peter Boveng; Dorothy M. Dick; Jerome Fiechter; Jaume Forcada; Karin A. Forney; Roger B. Griffis; et al. (Frontiers in Marine Science, 2017)

High but not moderate-intensity endurance training increases pain tolerance: a randomised trial - Thomas J. O’Leary; Johnny Collett; Ken Howells; Martyn G. Morris (European Journal of Applied Physiology, 2017)

Mechanisms of hepatotoxicity associated with the monocyclic β-lactam antibiotic BAL30072 - Franziska Paech; Simon Messner; Jochen Spickermann; Mathias Wind; Anne-Hortense Schmitt-Hoffmann; Anne Therese Witschi; Brett A. Howell; Rachel J. Church; Jeff Woodhead; Marc Engelhardt; Stephan Krähenbühl; Martina Maurer (Archives of Toxicology, 2017)

Variation in particulate C : N : P stoichiometry across the Lake Erie watershed from tributaries to its outflow - Clay Prater; Paul C. Frost; E. Todd Howell; Susan B. Watson; Arthur Zastepa; Sarah S. E. King; Richard J. Vogt; Marguerite A. Xenopoulos (Limnology and Oceanography, 2017)
Human activities can cause large alterations in biogeochemical cycles of key nutrients such as carbon (C), nitrogen (N), and phosphorus (P). However, relatively little is known about how these changes alter the proportional fluxes of these elements across ecosystem boundaries from rivers to lakes. Here, we examined environmental factors influencing spatial and temporal variation in particulate C : N : P ratios across the Lake Erie watershed from its tributaries to its outflow. Throughout the study, particulate nutrient ratios ranged widely (C : N 2.0–25.8, C : P 32–530, N : P 3.7–122.9), but mean values were generally lower than previous estimates from different aquatic environments. Particulate C : N ratios varied the least across all environments, but C : P and N : P ratios increased between tributaries and coastal areas and throughout the growing season in coastal environments. These ratios also differed temporally in offshore waters as particulate C : P and N : P were higher in the spring and summer and lower in the fall and winter. Particulate C : P ratios also increased between the western/central and eastern basins indicating differential nutrient processing across the lake. These stoichiometric changes were associated with unique environmental factors among ecosystems as tributary stoichiometry was related to terrestrial land use and land cover, coastal ratios were a product of mixing between riverine and offshore waters, and offshore patterns were influenced by differences in temperature and particulate nutrient loading among basins. Overall, by studying changes in particulate C : N : P ratios across the Lake Erie watershed, our study demonstrates the power of using mass balance principles to study nutrient transformations along the aquatic continuum.

Test–retest reliability of two consecutive mean sleep latency tests in patients with hypersomnia - Younghoon Kwon; Louis Kazaglis; Yeilim Cho; Michael J. Howell; Mark W. Mahowald (Sleep and Biological Rhythms, 2017)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Population genetics of reef coral endosymbionts ( Symbiodinium , Dinophyceae) - D. J. Thornhill; E. J. Howells; D. C. Wham; T. D. Steury; S. R. Santos (Molecular Ecology, 2017)
Symbiodinium is a diverse genus of unicellular dinoflagellate symbionts associating with various marine protists and invertebrates. Although the broadscale diversity and phylogenetics of the Symbiodinium complex is well established, there have been surprisingly few data on fine‐scale population structure and biogeography of these dinoflagellates. Yet population‐level processes contribute strongly to the biology of Symbiodinium , including how anthropogenic‐driven global climate change impacts these symbionts and their host associations. Here, we present a synthesis of population‐level characteristics for Symbiodinium , with an emphasis on how phylogenetic affinities, dynamics within and among host individuals, and a propensity towards clonality shape patterns on and across reefs. Major inferences include the following: (i) Symbiodinium populations within individual hosts are comprised mainly of cells belonging to a single or few genetic clones. (ii) Symbiont populations exhibit a mixed mode of reproduction, wherein at least one sexual recombination event occurs in the genealogy between most genotypes, but clonal propagation predominates overall. (iii) Mutualistic Symbiodinium do not perpetually persist outside their hosts, instead undergoing turnover and replacement via the continuous shedding of viable clonal cells from host individuals. (iv) Symbiont populations living in the same host, but on different reefs, are often genetically subdivided, suggesting low connectivity, adaptation to local conditions, or prolific asexual reproduction and low effective population sizes leading to disproportionate success within and among hosts. Overall, this synthesis forms a basis for future investigations of coral symbiosis ecology and evolution as well as delimitation of species boundaries in Symbiodinium and other eukaryotic microorganisms.

Risk algorithms that include pathology adjustment for HER2 amplification need to make further downward adjustments in likelihood scores - D. G. Evans; E. R. Woodward; S. J. Howell; S. Verhoef; A. Howell; F. Lalloo (Familial Cancer, 2017)

Ecological Role of Submarine Canyons and Need for Canyon Conservation: A Review - Ulla Fernandez-Arcaya; Eva Ramirez-Llodra; Jacopo Aguzzi; A. Louise Allcock; Jaime S. Davies; Awantha Dissanayake; Peter Harris; Kerry Howell; Veerle A. I. Huvenne; Miles Macmillan-Lawler; Jacobo Martín; Lenaick Menot; et al. (Frontiers in Marine Science, 2017)

Complexity and health functionality of plant cell wall fibers from fruits and vegetables - A. Padayachee; L. Day; K. Howell; M. J. Gidley (Critical Reviews in Food Science and Nutrition, 2017)

Reduced glutamate in white matter of male neonates exposed to alcohol in utero: a 1H-magnetic resonance spectroscopy study - F. M. Howells; K. A. Donald; A. Roos; R. P. Woods; H. J. Zar; K. L. Narr; D. J. Stein (Metabolic Brain Disease, 2016)

Land cover change and carbon emissions over 100 years in an A frican biodiversity hotspot - Simon Willcock; Oliver L. Phillips; Philip J. Platts; Ruth D. Swetnam; Andrew Balmford; Neil D. Burgess; Antje Ahrends; Julian Bayliss; Nike Doggart; Kathryn Doody; Eibleis Fanning; Jonathan M. H. Green; et al. (Global Change Biology, 2016)
Agricultural expansion has resulted in both land use and land cover change ( LULCC ) across the tropics. However, the spatial and temporal patterns of such change and their resulting impacts are poorly understood, particularly for the presatellite era. Here, we quantify the LULCC history across the 33.9 million ha watershed of Tanzania's Eastern Arc Mountains, using geo‐referenced and digitized historical land cover maps (dated 1908, 1923, 1949 and 2000). Our time series from this biodiversity hotspot shows that forest and savanna area both declined, by 74% (2.8 million ha) and 10% (2.9 million ha), respectively, between 1908 and 2000. This vegetation was replaced by a fivefold increase in cropland, from 1.2 million ha to 6.7 million ha. This LULCC implies a committed release of 0.9 Pg C (95% CI : 0.4–1.5) across the watershed for the same period, equivalent to 0.3 Mg C ha −1 yr −1 . This is at least threefold higher than previous estimates from global models for the same study area. We then used the LULCC data from before and after protected area creation, as well as from areas where no protection was established, to analyse the effectiveness of legal protection on land cover change despite the underlying spatial variation in protected areas. We found that, between 1949 and 2000, forest expanded within legally protected areas, resulting in carbon uptake of 4.8 (3.8–5.7) Mg C ha −1 , compared to a committed loss of 11.9 (7.2–16.6) Mg C ha −1 within areas lacking such protection. Furthermore, for nine protected areas where LULCC data are available prior to and following establishment, we show that protection reduces deforestation rates by 150% relative to unprotected portions of the watershed. Our results highlight that considerable LULCC occurred prior to the satellite era, thus other data sources are required to better understand long‐term land cover trends in the tropics.

Host adaptation and unexpected symbiont partners enable reef‐building corals to tolerate extreme temperatures - Emily J. Howells; David Abrego; Eli Meyer; Nathan L. Kirk; John A. Burt (Global Change Biology, 2016)
Understanding the potential for coral adaptation to warming seas is complicated by interactions between symbiotic partners that define stress responses and the difficulties of tracking selection in natural populations. To overcome these challenges, we characterized the contribution of both animal host and symbiotic algae to thermal tolerance in corals that have already experienced considerable warming on par with end‐of‐century projections for most coral reefs. Thermal responses in Platygyra daedalea corals from the hot Persian Gulf where summer temperatures reach 36°C were compared with conspecifics from the milder Sea of Oman. Persian Gulf corals had higher rates of survival at elevated temperatures (33 and 36°C) in both the nonsymbiotic larval stage (32–49% higher) and the symbiotic adult life stage (51% higher). Additionally, Persian Gulf hosts had fixed greater potential to mitigate oxidative stress (31–49% higher) and their Symbiodinium partners had better retention of photosynthetic performance under elevated temperature (up to 161% higher). Superior thermal tolerance of Persian Gulf vs. Sea of Oman corals was maintained after 6‐month acclimatization to a common ambient environment and was underpinned by genetic divergence in both the coral host and symbiotic algae. In P. daedalea host samples, genomewide SNP variation clustered into two discrete groups corresponding with Persian Gulf and Sea of Oman sites. Symbiodinium within host tissues predominantly belonged to ITS 2 rDNA type C3 in the Persian Gulf and type D1a in the Sea of Oman contradicting patterns of Symbiodinium thermal tolerance from other regions. Our findings provide evidence that genetic adaptation of both host and Symbiodinium has enabled corals to cope with extreme temperatures in the Persian Gulf. Thus, the persistence of coral populations under continued warming will likely be determined by evolutionary rates in both, rather than single, symbiotic partners.

Microsatellite allele sizes alone are insufficient to delineate species boundaries in Symbiodinium - E. J. Howells; B. L. Willis; L. K. Bay; M. J. H. van Oppen (Molecular Ecology, 2016)
Symbiodinium are a diverse group of unicellular dinoflagellates that are important nutritional symbionts of reef‐building corals. Symbiodinium putative species (‘types’) are commonly identified with genetic markers, mostly nuclear and chloroplast encoded ribosomal DNA regions. Population genetic analyses using microsatellite loci have provided insights into Symbiodinium biogeography, connectivity and phenotypic plasticity, but are complicated by: (i) a lack of consensus criteria used to delineate inter‐ vs. intragenomic variation within species; and (ii) the high density of Symbiodinium in host tissues, which results in single samples comprising thousands of individuals. To address this problem, Wham & LaJeunesse (2016) present a method for identifying cryptic Symbiodinium species from microsatellite data based on correlations between allele size distributions and nongeographic genetic structure. Multilocus genotypes that potentially do not recombine in sympatry are interpreted as secondary ‘species’ to be discarded from downstream population genetic analyses. However, Symbiodinium species delineations should ideally incorporate multiple physiological, ecological and molecular criteria. This is because recombination tests may be a poor indicator of species boundaries in Symbiodinium due to their predominantly asexual mode of reproduction. Furthermore, discontinuous microsatellite allele sizes in sympatry may be explained by secondary contact between previously isolated populations and by mutations that occur in a nonstepwise manner. Limitations of using microsatellites alone to delineate species are highlighted in earlier studies that demonstrate occasional bimodal distributions of allele sizes within Symbiodinium species and considerable allele size sharing among Symbiodinium species. We outline these issues and discuss the validity of reinterpretations of our previously published microsatellite data from Symbiodinium populations on the Great Barrier Reef (Howells et al . 2013).

A trans‐Atlantic examination of haddock Melanogrammus aeglefinus food habits - J. C. Tam; J. S. Link; S. I. Large; B. Bogstad; A. Bundy; A. M. Cook; G. E. Dingsør; A. V. Dolgov; D. Howell; A. Kempf; J. K. Pinnegar; A. Rindorf; et al. (Journal of Fish Biology, 2016)
The food habits of Melanogrammus aeglefinus were explored and contrasted across multiple north‐eastern and north‐western Atlantic Ocean ecosystems, using databases that span multiple decades. The results show that among all ecosystems, echinoderms are a consistent part of M. aeglefinus diet, but patterns emerge regarding where and when M. aeglefinus primarily eat fishes v . echinoderms. Melanogrammus aeglefinus does not regularly exhibit the increase in piscivory with ontogeny that other gadoids often show, and in several ecosystems there is a lower occurrence of piscivory. There is an apparent inverse relationship between the consumption of fishes and echinoderms in M. aeglefinus over time, where certain years show high levels of one prey item and low levels of the other. This apparent binary choice can be viewed as part of a gradient of prey options, contingent upon a suite of factors external to M. aeglefinus dynamics. The energetic consequences of this prey choice are discussed, noting that in some instances it may not be a choice at all.

Alcohol exposure in utero is associated with decreased gray matter volume in neonates - Kirsten A. Donald; J. P. Fouche; Annerine Roos; Nastassja Koen; Fleur M. Howells; Edward P. Riley; Roger P. Woods; Heather J. Zar; Katherine L. Narr; Dan J. Stein (Metabolic Brain Disease, 2016)

Genetic predisposition and early life experience interact to determine glutamate transporter (GLT1) and solute carrier family 12 member 5 (KCC2) levels in rat hippocampus - Toni-Lee Sterley; Fleur M. Howells; Jacqueline J. Dimatelis; Vivienne A. Russell (Metabolic Brain Disease, 2016)

Risk of contralateral breast cancer in BRCA1 and BRCA2 mutation carriers: a 30-year semi-prospective analysis - N. N. Basu; S. Ingham; J. Hodson; F. Lalloo; M. Bulman; A. Howell; D. G. Evans (Familial Cancer, 2015)

MITOsym®: A Mechanistic, Mathematical Model of Hepatocellular Respiration and Bioenergetics - Y. Yang; S. Nadanaciva; Y. Will; J. L. Woodhead; B. A. Howell; P. B. Watkins; S. Q. Siler (Pharmaceutical Research, 2015)

Functional connectivity in frontal-striatal brain networks and cocaine self-administration in female rhesus monkeys - K. S. Murnane; K. S. Gopinath; E. Maltbie; J. B. Daunais; Q. K. Telesford; L. L. Howell (Psychopharmacology, 2015)

Enhancing the TurtleWatch product for leatherback sea turtles, a dynamic habitat model for ecosystem‐based management - Evan A. Howell; Aimee Hoover; Scott R. Benson; Helen Bailey; Jeffrey J. Polovina; Jeffrey A. Seminoff; Peter H. Dutton (Fisheries Oceanography, 2015)
Fishery management measures to reduce interactions between fisheries and endangered or threatened species have typically relied on static time‐area closures. While these efforts have reduced interactions, they can be costly and inefficient for managing highly migratory species such as sea turtles. The NOAA TurtleWatch product was created in 2006 as a tool to reduce the rates of interactions of loggerhead sea turtles with shallow‐set longline gear deployed by the Hawaii‐based pelagic longline fishery targeting swordfish. TurtleWatch provides information on loggerhead habitat and can be used by managers and industry to make dynamic management decisions to potentially reduce incidentally capturing turtles during fishing operations. TurtleWatch is expanded here to include information on endangered leatherback turtles to help reduce incidental capture rates in the central North Pacific. Fishery‐dependent data were combined with fishing effort, bycatch and satellite tracking data of leatherbacks to characterize sea surface temperature ( SST ) relationships that identify habitat or interaction ‘hotspots’. Analysis of SST identified two zones, centered at 17.2° and 22.9°C, occupied by leatherbacks on fishing grounds of the Hawaii‐based swordfish fishery. This new information was used to expand the TurtleWatch product to provide managers and industry near real‐time habitat information for both loggerheads and leatherbacks. The updated TurtleWatch product provides a tool for dynamic management of the Hawaii‐based shallow‐set fishery to aid in the bycatch reduction of both species. Updating the management strategy to dynamically adapt to shifts in multi‐species habitat use through time is a step towards an ecosystem‐based approach to fisheries management in pelagic ecosystems.

Applying association mapping and genomic selection to the dissection of key traits in elite European wheat - Alison R. Bentley; Marco Scutari; Nicolas Gosman; Sebastien Faure; Felicity Bedford; Phil Howell; James Cockram; Gemma A. Rose; Tobias Barber; Jose Irigoyen; Richard Horsnell; Claire Pumfrey; et al. (Theoretical and Applied Genetics, 2014)

The Jeffries–Matusita distance for the case of complex Wishart distribution as a separability criterion for fully polarimetric SAR data - M. Dabboor; S. Howell; M. Shokr; J. Yackel (International Journal of Remote Sensing, 2014)

Persistence and stability of Eastern Afromontane forests: evidence from brevicipitid frogs - Simon P. Loader; F. Sara Ceccarelli; Michele Menegon; Kim M. Howell; Roman Kassahun; Abebe A. Mengistu; Samy A. Saber; Fikirte Gebresenbet; Rafael de Sá; Tim R. B. Davenport; Joanna G. Larson; Hendrik Müller; et al. (Journal of Biogeography, 2014)
Aim The persistence and stability of habitats through time are considered predictors of high levels of biodiversity in some environments. Long‐term habitat persistence and stability may explain the species‐rich, endemic forest fauna and flora of the Eastern Afromontane Biodiversity Region ( EABR ). Using complementary phylogenetic and biogeographical approaches, we examine evolutionary patterns in EABR brevicipitid frogs. Using these data, we test whether brevicipitid history reflects patterns of long‐term forest persistence and/or stability across the EABR . Location East Africa. Methods A dated phylogeny for brevicipitids was constructed using two nuclear and three mitochondrial markers. Alternative diversification models were used to determine signal for constant or varying net diversification rates. Using our dated tree, we identified areas of high phylogenetic diversity ( PD ), and inferred ancestral areas using likelihood and Bayesian approaches. Results Brevicipitids have a long history, with generic diversification among extant lineages pre‐dating the Oligocene (> 33 Ma). Ancestral‐area reconstructions indicate the presence of brevicipitids in the EABR since the Oligocene, and support a scenario of palaeoendemics surviving in EABR refugia. Ancestral‐area reconstructions indicate that the central Eastern Arc Mountains ( EAM ) formed the initial centre of diversification of forest brevicipitids. Measures of PD show that diversity varies across the EABR but is highest in the EAM . Constant net diversification rate in brevicipitids is a significantly better fit than alternative, rate‐variable models. Main conclusions The degree of persistence of forest habitats appears to be a contributing factor to the varying levels of diversity across the EABR in brevicipitids (and other organisms). In contrast to the Southern Highlands and Ethiopian Bale Mountains, the EAM stands out as an area that enabled the constant accumulation of brevicipitid species over a long period of time.

Structural brain changes in prenatal methamphetamine-exposed children - Annerine Roos; Gaby Jones; Fleur M. Howells; Dan J. Stein; Kirsten A. Donald (Metabolic Brain Disease, 2014)

Mindfulness based cognitive therapy may improve emotional processing in bipolar disorder: pilot ERP and HRV study - Fleur M. Howells; H. G. Laurie Rauch; Victoria L. Ives-Deliperi; Neil R. Horn; Dan J. Stein (Metabolic Brain Disease, 2014)

Mammographic surveillance in women aged 35–39 at enhanced familial risk of breast cancer (FH02) - D. G. Evans; S. Thomas; J. Caunt; L. Roberts; A. Howell; M. Wilson; R. Fox; D. M. Sibbering; S. Moss; M. G. Wallis; D. M. Eccles; S. Duffy (Familial Cancer, 2014)

Climate-induced primary productivity change and fishing impacts on the Central North Pacific ecosystem and Hawaii-based pelagic longline fishery - Evan A. Howell; Colette C. C. Wabnitz; John P. Dunne; Jeffrey J. Polovina (Climatic Change, 2013)

Spatial and temporal genetic structure of S ymbiodinium populations within a common reef‐building coral on the G reat B arrier R eef - Emily J. Howells; Bette L. Willis; Line K. Bay; Madeleine J. H. van Oppen (Molecular Ecology, 2013)
The dinoflagellate photosymbiont Symbiodinium plays a fundamental role in defining the physiological tolerances of coral holobionts, but little is known about the dynamics of these endosymbiotic populations on coral reefs. Sparse data indicate that Symbiodinium populations show limited spatial connectivity; however, no studies have investigated temporal dynamics for in hospite Symbiodinium populations following significant mortality and recruitment events in coral populations. We investigated the combined influences of spatial isolation and disturbance on the population dynamics of the generalist Symbiodinium type C2 ( ITS 1 rDNA ) hosted by the scleractinian coral Acropora millepora in the central Great Barrier Reef. Using eight microsatellite markers, we genotyped Symbiodinium in a total of 401 coral colonies, which were sampled from seven sites across a 12‐year period including during flood plume–induced coral bleaching. Genetic differentiation of Symbiodinium was greatest within sites, explaining 70–86% of the total genetic variation. An additional 9–27% of variation was explained by significant differentiation of populations among sites separated by 0.4–13 km, which is consistent with low levels of dispersal via water movement and historical disturbance regimes. Sampling year accounted for 6–7% of total genetic variation and was related to significant coral mortality following severe bleaching in 1998 and a cyclone in 2006. Only 3% of the total genetic variation was related to coral bleaching status, reflecting generally small (8%) reductions in allelic diversity within bleached corals. This reduction probably reflected a loss of genotypes in hospite during bleaching, although no site‐wide changes in genetic diversity were observed. Combined, our results indicate the importance of disturbance regimes acting together with limited oceanographic transport to determine the genetic composition of Symbiodinium types within reefs.

Novel Mutations Mapping to the Fourth Sodium Channel Domain of Nav1.7 Result in Variable Clinical Manifestations of Primary Erythromelalgia - Roman Cregg; Bisola Laguda; Robert Werdehausen; James J. Cox; John E. Linley; Juan D. Ramirez; Istvan Bodi; Michael Markiewicz; Kevin J. Howell; Ya-Chun Chen; Karen Agnew; Henry Houlden; et al. (NeuroMolecular Medicine, 2013)

Genetic characterization and mapping of the Rht-1 homoeologs and flanking sequences in wheat - Edward P. Wilhelm; Rhian M. Howells; Nadia Al-Kaff; Jizeng Jia; Catherine Baker; Michelle A. Leverington-Waite; Simon Griffiths; Andy J. Greenland; Margaret I. Boulton; Wayne Powell (Theoretical and Applied Genetics, 2013)

Historical thermal regimes define limits to coral acclimatization - Emily J. Howells; Ray Berkelmans; Madeleine J. H. van Oppen; Bette L. Willis; Line K. Bay (Ecology, 2013)
Knowledge of the degree to which corals undergo physiological acclimatization or genetic adaptation in response to changes in their thermal environment is crucial to the success of coral reef conservation strategies. The potential of corals to acclimatize to temperatures exceeding historical thermal regimes was investigated by reciprocal transplantation of Acropora millepora colonies between the warm central and cool southern regions of the Great Barrier Reef (GBR) for a duration of 14 months. Colony fragments retained at native sites remained healthy, whereas transplanted fragments, although healthy over initial months when temperatures remained within native thermal regimes, subsequently bleached and suffered mortality during seasonal temperature extremes. Corals hosting Symbiodinium D transplanted to the southern GBR bleached in winter and the majority suffered whole (40%; n = 20 colonies) or partial (50%) mortality at temperatures 1.1°C below their 15‐year native minimum. In contrast, corals hosting Symbiodinium C2 transplanted to the central GBR bleached in summer and suffered whole (50%; n = 10 colonies) or partial (42%) mortality at temperatures 2.5°C above their 15‐year native maximum. During summer bleaching, the dominant Symbiodinium type changed from C2 to D within corals transplanted to the central GBR. Corals transplanted to the cooler, southern GBR grew 74–80% slower than corals at their native site, and only 50% of surviving colonies reproduced, at least partially because of cold water bleaching of transplants. Despite the absence of any visual signs of stress, corals transplanted to the warmer, central GBR grew 52–59% more slowly than corals at their native site before the summer bleaching (i.e., from autumn to spring). Allocation of energy to initial acclimatization or reproduction may explain this pattern, as the majority (65%) of transplants reproduced one month earlier than portions of the same colonies retained at the southern native site. All parameters investigated (bleaching, mortality, Symbiodinium type fidelity, reproductive timing) demonstrated strong interactions between genotype and environment, indicating that the acclimatization potential of A. millepora populations may be limited by adaptation of the holobiont to native thermal regimes.

Close-range hyperspectral imaging for geological field studies: workflow and methods - Tobias H. Kurz; Simon J. Buckley; John A. Howell (International Journal of Remote Sensing, 2013)

The Development of the Washington State Emergency Department Opioid Prescribing Guidelines - Darin E. Neven; Jennifer C. Sabel; Donelle N. Howell; Russell J. Carlisle (Journal of Medical Toxicology, 2012)

Platelet development in cuboid diamonds: insights from micro-FTIR mapping - D. Howell; C. J. O’Neill; K. J. Grant; W. L. Griffin; S. Y. O’Reilly; N. J. Pearson; R. A. Stern; T. Stachel (Contributions to Mineralogy and Petrology, 2012)

Variability and change in the Canadian cryosphere - C. Derksen; S. L. Smith; M. Sharp; L. Brown; S. Howell; L. Copland; D. R. Mueller; Y. Gauthier; C. G. Fletcher; A. Tivy; M. Bernier; J. Bourgeois; et al. (Climatic Change, 2012)
During the International Polar Year (IPY), comprehensive observational research programs were undertaken to increase our understanding of the Canadian polar cryosphere response to a changing climate. Cryospheric components considered were snow, permafrost, sea ice, freshwater ice, glaciers and ice shelves. Enhancement of conventional observing systems and retrieval algorithms for satellite measurements facilitated development of a snapshot of current cryospheric conditions, providing a baseline against which future change can be assessed. Key findings include: 1. surface air temperatures across the Canadian Arctic exhibit a warming trend in all seasons over the past 40 years. A consistent pan-cryospheric response to these warming temperatures is evident through the analysis of multi-decadal datasets; 2. in recent years (including the IPY period) a higher rate of change was observed compared to previous decades including warming permafrost, reduction in snow cover extent and duration, reduction in summer sea ice extent, increased mass loss from glaciers, and thinning and break-up of the remaining Canadian ice shelves. These changes illustrate both a reduction in the spatial extent and mass of the cryosphere and an increase in the temporal persistence of melt related parameters. The observed changes in the cryosphere have important implications for human activity including the close ties of northerners to the land, access to northern regions for natural resource development, and the integrity of northern infrastructure.

In vitro to in vivo extrapolation and species response comparisons for drug-induced liver injury (DILI) using DILIsym™: a mechanistic, mathematical model of DILI - Brett A. Howell; Yuching Yang; Rukmini Kumar; Jeffrey L. Woodhead; Alison H. Harrill; Harvey J. Clewell; Melvin E. Andersen; Scott Q. Siler; Paul B. Watkins (Journal of Pharmacokinetics and Pharmacodynamics, 2012)

Population Pharmacokinetics and Pharmacodynamics of Ribavirin in Patients with Chronic Hepatitis C Genotype 1 Infection - Runyan Jin; Michael J. Fossler; John G. McHutchison; Charles D. Howell; Thomas C. Dowling (The AAPS Journal, 2012)

Synergistic tonic and phasic activity of the locus coeruleus norepinephrine (LC-NE) arousal system is required for optimal attentional performance - Fleur M. Howells; Dan J. Stein; Vivienne A. Russell (Metabolic Brain Disease, 2012)

The Pel and Psl polysaccharides provide Pseudomonas aeruginosa structural redundancy within the biofilm matrix - Kelly M. Colvin; Yasuhiko Irie; Catherine S. Tart; Rodolfo Urbano; John C. Whitney; Cynthia Ryder; P. Lynne Howell; Daniel J. Wozniak; Matthew R. Parsek (Environmental Microbiology, 2012)
Summary Extracellular polysaccharides comprise a major component of the biofilm matrix. Many species that are adept at biofilm formation have the capacity to produce multiple types of polysaccharides. Pseudomonas aeruginosa produces at least three extracellular polysaccharides, alginate, Pel and Psl, that have been implicated in biofilm development. Non‐mucoid strains can use either Pel or Psl as the primary matrix structural polysaccharide. In this study, we evaluated a range of clinical and environmental P. aeruginosa isolates for their dependence on Pel and Psl for biofilm development. Mutational analysis demonstrates that Psl plays an important role in surface attachment for most isolates. However, there was significant strain‐to‐strain variability in the contribution of Pel and Psl to mature biofilm structure. This analysis led us to propose four classes of strains based upon their Pel and Psl functional and expression profiles. Our data also suggest that Pel and Psl can serve redundant functions as structural scaffolds in mature biofilms. We propose that redundancy could help preserve the capacity to produce a biofilm when exopolysaccharide genes are subjected to mutation. To test this, we used PAO1, a common lab strain that primarily utilizes Psl in the matrix. As expected, a psl mutant strain initially produced a poor biofilm. After extended cultivation, we demonstrate that this strain acquired mutations that upregulated expression of the Pel polysaccharide, demonstrating the utility of having a redundant scaffold exopolysaccharide. Collectively, our studies revealed both unique and redundant roles for two distinct biofilm exopolysaccharides.

Estimating the carrying capacity of French Frigate Shoals for the endangered Hawaiian monk seal using Ecopath with Ecosim - Frank A. Parrish; Evan A. Howell; George A. Antonelis; Sara J. Iverson; Charles L. Littnan; James D. Parrish; Jeffrey J. Polovina (Marine Mammal Science, 2012)
The carrying capacity of the French Frigate Shoals (FFS) region for the endangered Hawaiian monk seal was appraised using an updated version of the original FFS Ecopath model ( Polovina 1984 ). Model parameters were updated using recent literature, and data from surveys of the seal population and its bottom‐associated prey. Together they produced a static mass balance model for 1998 when the prey surveys began. The Ecopath‐estimated monk seal biomass was 0.0045 t/km 2 , which was in close agreement with the biomass calculated from monk seal field beach counts (0.0046 t/km 2 ). Model simulations through time were done in Ecosim using the Ecopath balanced model and included fisheries data time series from 1998 to 2008. Monk seal biomass declined concurrently with decreases in benthic bottomfish biomass, which were influenced by large‐scale changes in the environment of the North Pacific. This model scenario was extended from 2010, when the last permitted fishery in the Northwestern Hawaiian Islands was closed, through to 2040, assuming a constant environmental signal. Model results for this time period did not show a recovery of monk seals that exceeded the initial 1998 model biomass levels, highlighting the importance of including environmental variability in estimates of monk seals recovery at FFS.

Detection of periodontal pathogens in newborns and children with mixed dentition - J. R. Cortelli; C. B. Fernandes; F. O. Costa; S. C. Cortelli; M. Kajiya; S. C. Howell; T. Kawai (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Solvent Removal and Spore Inactivation Directly in Dispensing Vials with Supercritical Carbon Dioxide and Sterilant - Jahna Howell; Fengui Niu; Shannon E. McCabe; Wei Zhou; Charles J. Decedue (AAPS PharmSciTech, 2012)

A directed miniscreen for genes involved in the Drosophila anti-parasitoid immune response - Laura Howell; Christopher J. Sampson; Miguel J. Xavier; Ekin Bolukbasi; Margarete M. S. Heck; Michael J. Williams (Immunogenetics, 2012)

Erratum to: Quantifying strain birefringence halos around inclusions in diamond - D. Howell; I. G. Wood; D. P. Dobson; A. P. Jones; L. Nasdala; J. W. Harris (Contributions to Mineralogy and Petrology, 2011)

Pacific Atmospheric Sulfur Experiment (PASE): dynamics and chemistry of the south Pacific tropical trade wind regime - Alan Bandy; Ian C. Faloona; Byron W. Blomquist; Barry J. Huebert; Antony D. Clarke; Steven G. Howell; R. L. Mauldin; Christopher A. Cantrell; James G. Hudson; Brian G. Heikes; John T. Merrill; Yuhang Wang; et al. (Journal of Atmospheric Chemistry, 2011)

Breast cancer susceptibility variants alter risk in familial ovarian cancer - A. Latif; H. J. McBurney; S. A. Roberts; F. Lalloo; A. Howell; D. G. Evans; W. G. Newman (Familial Cancer, 2010)

Quantifying strain birefringence halos around inclusions in diamond - D. Howell; I. G. Wood; D. P. Dobson; A. P. Jones; L. Nasdala; J. W. Harris (Contributions to Mineralogy and Petrology, 2010)

Preparing for climate change in Washington State - Lara C. Whitely Binder; Jennifer Krencicki Barcelos; Derek B. Booth; Meriel Darzen; Marketa McGuire Elsner; Richard Fenske; Thomas F. Graham; Alan F. Hamlet; John Hodges-Howell; J. Elizabeth Jackson; Catherine Karr; Patrick W. Keys; et al. (Climatic Change, 2010)

RASSF1A polymorphism in familial breast cancer - J. Bergqvist; A. Latif; S. A. Roberts; K. D. Hadfield; F. Lalloo; A. Howell; D. G. Evans; W. G. Newman (Familial Cancer, 2010)

Oceanographic influences on the dive behavior of juvenile loggerhead turtles (Caretta caretta) in the North Pacific Ocean - Evan A. Howell; Peter H. Dutton; Jeffrey J. Polovina; Helen Bailey; Denise M. Parker; George H. Balazs (Marine Biology, 2010)

The importance and value of EQA for diagnostic genetic laboratories - Ros J. Hastings; Rod T. Howell (Journal of Community Genetics, 2010)

Non-timber forest product dependence among the Jah Hut subgroup of Peninsular Malaysia’s Orang Asli - Colleen J. Howell; Kurt A. Schwabe; Azizan Haji Abu Samah (Environment, Development and Sustainability, 2010)

Isolation, characterisation and cross amplification of thirteen microsatellite loci for coral endo-symbiotic dinoflagellates (Symbiodinium clade C) - Line Kolind Bay; Emily J. Howells; Madeleine J. H. van Oppen (Conservation Genetics Resources, 2009)

Mitochondrial DNA divergence in the critically imperilled pygmy madtom, Noturus stanauli (Siluriformes: Ictaluridae) - M. G. Bennett; J. Heath Howell; B. R. Kuhajda; R. M. Wood (Journal of Fish Biology, 2009)
The mitochondrial cytochrome b gene was sequenced for six individuals of the pygmy madtom, Noturus stanauli , a globally imperilled catfish, from both known localities in Tennessee (U.S.A.) separated by over 1055 river km. Phylogenetic and population genetic analyses revealed little divergence between these populations for this locus.

Radiometric surface temperature calibration effects on satellite based evapotranspiration estimation - J. L. Chávez; P. H. Gowda; T. A. Howell; K. S. Copeland (International Journal of Remote Sensing, 2009)

High genetic differentiation and cross-shelf patterns of genetic diversity among Great Barrier Reef populations of Symbiodinium - E. J. Howells; M. J. H. van Oppen; B. L. Willis (Coral Reefs, 2009)

Remote sensing of contrasting tillage practices in the Texas Panhandle - Prasanna H. Gowda; T. A. Howell; S. R. Evett; J. L. Chavez; L. New (International Journal of Remote Sensing, 2008)

Using bomb radiocarbon analyses to validate age and growth estimates for the tiger shark, Galeocerdo cuvier, in the western North Atlantic - Jeff Kneebone; Lisa J. Natanson; Allen H. Andrews; W. Hunt Howell (Marine Biology, 2008)

Mapping of a gene (Vir) for a non-glaucous, viridescent phenotype in bread wheat derived from Triticum dicoccoides, and its association with yield variation - J. R. Simmonds; L. J. Fish; M. A. Leverington-Waite; Y. Wang; P. Howell; J. W. Snape (Euphytica, 2008)

Does sequence polymorphism of FLC paralogues underlie flowering time QTL in Brassica oleracea? - H. Razi; E. C. Howell; H. J. Newbury; M. J. Kearsey (Theoretical and Applied Genetics, 2008)

Using the composite variables of reproductive morphology, histology and steroid hormones to determine age and size at sexual maturity for the thorny skate Amblyraja radiata in the western Gulf of Maine - J. A. Sulikowski; J. Kneebone; S. Elzey; J. Jurek; W. H. Howell; P. C. W. Tsang (Journal of Fish Biology, 2006)
Age at size was linked to sexual maturity in 77 male and 93 female thorny skates Amblyraja radiata from the western Gulf of Maine using three criteria: 1) gross reproductive morphology, 2) histology and 3) steroid hormone concentrations. Age‐bias plots and the coefficient of variation from vertebral band counts suggested that the ageing method represented a non‐biased and precise approach to the age assessment of A. radiata . Maturity ogives for males, based on data gathered for clasper length, circulating testosterone concentrations and proportion of mature spermatocysts within the testes, predicted that 50% maturity occurred at a total length ( L T ) of 865 mm and c. 10·90 years of age. For females, maturity ogives, based on data gathered for ovary mass, shell gland mass, follicle size and circulating oestradiol concentrations, predicted that 50% maturity occurred at 875 mm L T and c. 11·00 years of age. Collectively, the results suggest that analysis of several contemporaneous reproductive variables offers an accurate determination of sexual maturity in the thorny skate.

Interleukin-10 Polymorphisms, Cancer Susceptibility and Prognosis - W. Martin Howell; Matthew J. Rose-Zerilli (Familial Cancer, 2006)

Does the mitochondrial genome play a role in the etiology of Alzheimer’s disease? - Joanna L. Elson; Corinna Herrnstadt; Gwen Preston; Leon Thal; Christopher M. Morris; J. A. Edwardson; M. Flint Beal; Douglass M. Turnbull; Neil Howell (Human Genetics, 2006)

Development of the dopamine transporter selective RTI-336 as a pharmacotherapy for cocaine abuse - F. Ivy Carroll; James L. Howard; Leonard L. Howell; Barbara S. Fox; Michael J. Kuhar (The AAPS Journal, 2006)

Characterisation of Pear blister canker viroid isolates from Australian pome fruit orchards - P.A. Joyce; F.E. Constable; J. Crosslin; K. Eastwell; W.E. Howell; B.C. Rodoni (Australasian Plant Pathology, 2006)

Transgenic rescue of the mouse t complex haplolethal locus Thl1 - Gareth R. Howell; Robert J. Munroe; John C. Schimenti (Mammalian Genome, 2005)

How much do valley fills influence headwater streams? - Kyle J. Hartman; Michael D. Kaller; John W. Howell; John A. Sweka (Hydrobiologia, 2005)

An annual cycle of steroid hormone concentrations and gonad development in the winter skate, Leucoraja ocellata , from the western Gulf of Maine - J. A. Sulikowski; P. C. W. Tsang; W. Huntting Howell (Marine Biology, 2004)

Forage and migration habitat of loggerhead ( Caretta caretta ) and olive ridley ( Lepidochelys olivacea ) sea turtles in the central North Pacific Ocean - Jeffrey J. Polovina; George H. Balazs; Evan A. Howell; Denise M. Parker; Michael P. Seki; Peter H. Dutton (Fisheries Oceanography, 2004)
Satellite telemetry from 26 loggerhead ( Caretta caretta ) and 10 olive ridley ( Lepidochelys olivacea ) sea turtles captured and released from pelagic longline fishing gear provided information on the turtles’ position and movement in the central North Pacific. These data together with environmental data from satellite remote sensing are used to describe the oceanic habitat used by these turtles. The results indicate that loggerheads travel westward, move seasonally north and south primarily through the region 28–40°N, and occupy sea surface temperatures (SST) of 15–25°C. Their dive depth distribution indicated that they spend 40% of their time at the surface and 90% of their time at depths

Respiratory gene expression in soybean cotyledons during post-germinative development - Daniel O. Daley; Michael J. Considine; Katharine A. Howell; A. Harvey Millar; David A. Day; James Whelan (Plant Molecular Biology, 2003)

Monitoring the Penetration Enhancer Dimethyl Sulfoxide in Human Stratum Corneum in Vivo by Confocal Raman Spectroscopy - Peter J. Caspers; Adrian C. Williams; Elizabeth A. Carter; Howell G. M. Edwards; Brian W. Barry; Hajo A. Bruining; Gerwin J. Puppels (Pharmaceutical Research, 2002)

Arsenic uptake and accumulation in rice (Oryza sativa L.) irrigated with contaminated water - Md. Joinal Abedin; J. Cotter-Howells; Andy A. Meharg (Plant and Soil, 2002)

Arabidopsis mutants with increased organ regeneration in tissue culture are more competent to respond to hormonal signals - Andrew Cary; Shyam J. Uttamchandani; Rafaël Smets; Harry A. Van Onckelen; Stephen H. Howell (Planta, 2001)

Modelling the influence of glacial isostasy on Late Weichselian ice-sheet growth in the Barents Sea - Daniel Howell; Martin J. Siegert; Julian A. Dowdeswell (Journal of Quaternary Science, 2000)

Sub-cellular Localisation of the White/Scarlet ABC Transporter to Pigment Granule Membranes Within the Compound Eye of Drosophila Melanogaster - Susan M. Mackenzie; Antony J. Howells; Graeme B. Cox; Gary D. Ewart (Genetica, 2000)

An integrated AFLP and RFLP Brassica oleracea linkage map from two morphologically distinct doubled-haploid mapping populations - R. L. Sebastian; E. C. Howell; G. J. King; D. F. Marshall; M. J. Kearsey (Theoretical and Applied Genetics, 2000)

Mercury Concentrations in Louisiana and Chinese Crayfish - L. J. Schuler; J. P. Howell; M. G. Heagler (Bulletin of Environmental Contamination and Toxicology, 2000)

Surface-Layer Fluxes in Stable Conditions - J. F. Howell; J. Sun (Boundary-Layer Meteorology, 1999)

The Student Watershed Research Project (SWRP): collecting watershed data for use by resource management agencies - Deborah J. Lev; Stacy L. Renfro; D. Torrey Lindbo; Wes Jarrell; Jane Blair; Steve Andrews; Lin Howell (Urban Ecosystems, 1998)

Morphological differences between wild and hatchery‐reared turbot - T. Ellis; B. R. Howell; J. Hayes (Journal of Fish Biology, 1997)
Reared 0‐group turbot originating from Irish Sea stock were heavier at a given length than wild fish due to a greater body width and body depth. A very high incidence (96%) of abnormal lateral line canals was noted in the reared fish. It is suggested that these morphometric and morphological differences developed during the larval stage.

Multiresolution Flux Decomposition - J. F. Howell; L. Mahrt (Boundary-Layer Meteorology, 1997)

Functions of the white and topaz loci of Lucilia cuprina in the production of the eye pigment xanthommatin - K. M. Summers; A. J. Howells (Biochemical Genetics, 1980)

Isolation and biochemical analysis of a temperature-sensitive scarlet eye color mutant of Drosophila melanogaster - A. J. Howells (Biochemical Genetics, 1979)

Xanthommatin biosynthesis in wild-type and mutant strains of the Australian sheep blowfly Lucilia cuprina - K. M. Summers; A. J. Howells (Biochemical Genetics, 1978)

Control of drosopterin synthesis in Drosophila melanogaster: Mutants showing an altered pattern of GTP cyclohydrolase activity during development - B. A. Evans; A. J. Howells (Biochemical Genetics, 1978)

Developmental patterns of 3-hydroxykynurenine accumulation in white and various other eye color mutants of Drosophila melanogaster - A. J. Howells; K. M. Summers; Rosemary L. Ryall (Biochemical Genetics, 1977)

The ommochrome biosynthetic pathway in Drosophila melanogaster: The head particulate phenoxazinone synthase and the developmental onset of xanthommatin synthesis - M. Yamamoto; A. J. Howells; Rosemary L. Ryall (Biochemical Genetics, 1976)

A biochemical study of the scarlet eye-color mutant of Drosophila melanogaster - A. J. Howells; Rosemary L. Ryall (Biochemical Genetics, 1975)

Levels of RNA and DNA in Drosophila melanogaster at different stages of development: A comparison between one bobbed and two phenotypically non-bobbed stocks - A. J. Howells (Biochemical Genetics, 1972)

Notes on the biology of a spider parasiteColpomeria kincaidii Ashmead [Hymenoptera: Ichneumonidae] - J. O. Howell; R. L. Pienkowski (BioControl, 1972)